Crystallized glass, crystallized glass product, and manufacturing method

By adjusting the composition of the crystalline glass and optimizing its chemical composition, the shortcomings of existing crystalline glass in terms of optical properties and chemical stability are solved, and the combination of high mechanical properties and excellent optical properties is achieved, making it suitable for high-performance display equipment and electronic equipment.

JP2025060820AInactive Publication Date: 2025-04-10CDGM OPTICAL GLASS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024227975
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-01-28
Filing Date
2024-12-24
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing crystalline glasses have shortcomings in optical properties and chemical stability, and are difficult to meet the needs of high-performance display equipment and electronic equipment.

Method used

By adjusting the composition of the crystalline glass, it specifically includes SiO2 65-80%, Al2O3 <5%, Li2O 10-25%, ZrO2 5-15%, P2O5 1-8%, and other oxides such as K2O, MgO, ZnO, Na2O, SrO, BaO, CaO, TiO2, B2O3, Y2O3, etc., to optimize their chemical composition to improve mechanical and optical properties.

Benefits of technology

The high mechanical properties and excellent optical properties of crystallized glass are achieved, including improved light transmission, reduced haze, enhanced impact resistance and wear resistance, making it suitable for high-performance display equipment and electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060820000001
    Figure 2025060820000001
  • Figure 2025060820000002
    Figure 2025060820000002
  • Figure 2025060820000003
    Figure 2025060820000003
Patent Text Reader

Abstract

To provide a crystallized glass product with excellent mechanical characteristics.SOLUTION: The crystallized glass product has a composition comprising, in mass percent, 65-80% of SiO2 component, less than 5% of an Al2O3 component, 10-25% of a Li2O component, 5-15% of a ZrO2 component, and 1-8% of a P2O5 component.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to crystallized glass, and more particularly to crystallized glass having excellent mechanical properties, a crystallized glass product, and a method for producing the same. [Background technology]

[0002] In recent years, with the rise and development of home electronics, glass is widely used in electronic devices as a transparent and high-performance material. Devices such as LED and LCD displays, as well as computer monitors, have a "touch" function, so the glass applied to the device must come into contact with various objects such as the user's finger and / or stylus pen device, and for this purpose, the glass must be robust and chemically stable enough to withstand conventional contact without damage. In addition, there is a possibility that the glass can be applied to portable electronic products such as mobile phones, tablets, and personal media terminals, which not only need to withstand normal "touch" contact for a long time, but also need to withstand accidental bending, scratches, and impacts that may occur during use, and therefore require higher performance glass.

[0003] Crystallized glass is a material made by reheating glass to precipitate crystals. It has better mechanical properties than conventional glass, and crystallization is formed in the glass, which makes it far superior to conventional glass in terms of bending resistance, abrasion resistance, drop resistance, etc. Meanwhile, the mechanical performance of crystallized glass can be further improved by chemical strengthening. Based on the above advantages, crystallized glass or crystallized glass products obtained after processing are currently used in front and rear covers of display devices or electronic devices, particularly portable electronic devices (e.g., mobile phones, watches, PADs, etc.), which require high drop resistance, compression resistance, scratch resistance, etc.

[0004] With the development of science and technology, the optical performance of glass materials used in electronic devices and display devices is the performance exhibited when a substance absorbs, reflects, and refracts light, and there is an increasing demand for light transmittance, haze, refractive index, etc. However, currently commercially available crystallized glass has problems such as poor chemical durability, high haze, and low light transmittance, making it difficult to apply it to display devices and electronic devices with high specifications.

[0005] Therefore, developing crystallized glass and crystallized glass products that have excellent mechanical properties and are suitable for display devices and electronic equipment has become a goal pursued by scientists and engineers. Summary of the Invention [Problem to be solved by the invention]

[0006] The technical problem to be solved by the present invention is to provide a crystallized glass having excellent mechanical properties and a crystallized glass. [Means for solving the problem]

[0007] The technical solutions adopted in the present invention to solve the technical problems are as follows:

[0008] (1) A crystallized glass product, the crystallized glass having, in terms of mass percentage of its composition, 65 to 80% of a SiO2 component, less than 5% of an Al2O3 component, 10 to 25% of a Li2O component, 5 to 15% of a ZrO2 component, and 1 to 8% of a P2O5 component.

[0009] (2) A crystallized glass product, the crystallized glass having a composition, by mass percentage, of 55 to 80% SiO2 component, less than 10% Al2O3 component, 8 to 25% Li2O component, 5 to 15% ZrO2 component, and 1 to 8% P2O5 component.

[0010] (3) The crystallized glass product according to (1) or (2) above, wherein the crystallized glass contains, in mass percent of its composition, 0-5% K2O, 0-3% MgO, 0-3% ZnO, 0-6% Na2O, 0-5% SrO, 0-5% BaO, 0-5% CaO, 0-5% TiO2, 0-5% B2O3, 0-6% Y2O3, and / or 0-2% fining agent.

[0011] (4) A crystallized glass product, comprising SiO2, Al2O3, Li2O, ZrO2 and P2O5 as components in its composition, said crystallized glass containing a lithium silicate crystal phase in a mass percentage higher than other crystal phases.

[0012] (5) A crystallized glass product, comprising crystallized glass containing SiO2, Li2O, ZrO2 and P2O5 as components, the crystallized glass having a thickness of 1 mm or less and an average light |B| value at 400 to 800 nm of 0.9 or less.

[0013] (6) The above crystallized glass containing a lithium silicate crystal phase and having a falling ball impact test height of 1,400 mm or more.

[0014] (7) Crystallized glass containing SiO2, Al2O3, Li2O, ZrO2 and P2O5 as its components, the mass percentage of the composition being Al2O3 / (P2O5+ZrO2) of 1.2 or less, containing a lithium silicate crystal phase, and having a falling ball impact test height of 1,400 mm or more.

[0015] (8) A crystallized glass containing SiO2, Li2O, ZrO2 and P2O5 as components, the crystallized glass having a SiO2 / ZrO2 ratio of 4.0 to 15.8 in terms of mass percent of the composition, containing a lithium silicate crystal phase, and having a higher mass percent than other crystal phases.

[0016] (9) The crystallized glass product according to any one of (4) to (8) above, the crystallized glass product having a composition, in mass percent, of 55 to 80% of a SiO2 component, and / or 8 to 25% of a Li2O component, and / or 5 to 15% of a ZrO2 component, and / or 1 to 8% of a P2O5 component.

[0017] (10) A crystallized glass product, the composition of which, in mass percent, is 55-80% of a SiO2 component, 8-25% of a Li2O component, 5-15% of a ZrO2 component, and 1-8% of a P2O5 component.

[0018] (11) The crystallized glass product according to any one of (4) to (10) above, wherein the crystallized glass has a composition, in mass percent, of less than 10% Al2O3 component, and / or 0 to 5% K2O component, and / or 0 to 3% MgO component, and / or 0 to 3% ZnO component, and / or 0 to 6% Na2O component, and / or 0 to 5% SrO component, and / or 0 to 5% BaO component, and / or 0 to 5% CaO component, and / or 0 to 5% TiO2 component, and / or 0 to 5% B2O3 component, and / or 0 to 6% Y2O3 component, and / or 0 to 2% fining agent.

[0019] (12) The crystallized glass product according to any one of (1) to (11) above, the composition of which satisfies, in mass percent, one or more of the following ten conditions: 1) Al2O3 / (P2O5+ZrO2) is 1.2 or less, preferably Al2O3 / (P2O5+ZrO2) is 1.0 or less, and more preferably Al2O3 / (P2O5+ZrO2) is 0.05 to 0.7. 2) SiO2 / ZrO2 is 4.0 to 15.8, preferably SiO2 / ZrO2 is 4.5 to 12.0, more preferably SiO2 / ZrO2 is 5.0 to 9.5, and further preferably SiO2 / ZrO2 is 6.0 to 9.0. 3) P2O5+ZrO2 is 6 to 21%, preferably P2O5+ZrO2 is 7 to 18%, more preferably P2O5+ZrO2 is 8 to 16%, and further preferably P2O5+ZrO2 is 10 to 16%. 4) SiO2 / (P2O5+ZrO2) is 2.5 to 12.0, preferably SiO2 / (P2O5+ZrO2) is 3.0 to 10.0, more preferably SiO2 / (P2O5+ZrO2) is 3.5 to 7.5, and even more preferably SiO2 / (P2O5+ZrO2) is 4.0 to 6.5. 5) (ZrO2+Li2O) / Al2O3 is 2.0 or more, preferably (ZrO2+Li2O) / Al2O3 is 2.5 or more, and more preferably ZrO2+Li2O) / Al2O3 is 2.5 to 30.0. 6) (SiO2+Al2O3) / ZrO2 is 4.0 to 16.0, preferably (SiO2+Al2O3) / ZrO2 is 4.5 to 12.0, more preferably (SiO2+Al2O3) / ZrO2 is 5.0 to 10.0, and even more preferably (SiO2+Al2O3) / ZrO2 is 6.0 to 9.5. 7) (Li2O+ZrO2) / SiO2 is 0.19 to 0.55, preferably (Li2O+ZrO2) / ZrO2 is 0.2 to 0.5, more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.45, and even more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.4. 8) (MgO+ZnO) / ZrO2 is 0.65 or less, preferably (MgO+ZnO) / ZrO2 is 0.4 or less, more preferably (MgO+ZnO) / ZrO2 is 0.2 or less, and even more preferably (MgO+ZnO) / ZrO2 is 0.1 or less. 9) (Li2O+Al2O3) / ZrO2 is 0.8 to 5.0, preferably (Li2O+Al2O3) / ZrO2 is 1.0 to 4.0, more preferably (Li2O+Al2O3) / ZrO2 is 1.2 to 3.0, and even more preferably (Li2O+Al2O3) / ZrO2 is 1.5 to 2.5. 10) Li2O / (ZrO2+P2O5) is 0.5 to 3.0, preferably Li2O / (ZrO2+P2O5) is 0.6 to 2.5, more preferably Li2O / (ZrO2+P2O5) is 0.7 to 2.0, and even more preferably Li2O / (ZrO2+P2O5) is 0.8 to 1.5.

[0020] (13) The crystallized glass product according to any one of (1) to (11), wherein the composition, in mass percent, of the crystallized glass product is Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.2, even more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.1, and / or Al2O3 / Li2O is 0.4 or less, preferably Al2O3 / Li2O is 0.3 or less, more preferably Al2O3 / Li2O is 0.2 or less, even more preferably Al2O3 / Li2O is 0.1 or less.

[0021] (14) The crystallized glass product according to any one of (1) to (11), wherein the composition is, in mass percent, 68 to 78% SiO2 component, preferably 70 to 76% SiO2 component, and / or 0.1 to 4.5% Al2O3 component, preferably 0.5 to 3% Al2O3 component, and / or 12.5 to 22% Li2O component, preferably 12.5 to 20% Li2O component, and / or 6 to 12% ZrO2 component, preferably 7 to 12% ZrO2 component, and / or 1.5 to 7% P2O5 component, preferably 2 to 6% P2O5 component, and / or 0 to 4% K2O component, preferably 0 to 2% K2O component, and / or 0 to 2% MgO component, preferably 0 to 1% MgO component, and / or ZrO2 component. the glass-ceramics containing 0-2% of a nO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent, preferably 0-0.5% of a fining agent.

[0022] (15) The crystallized glass product according to any one of (2), (4) to (11), wherein the composition, in mass percent, of Al2O3 / (Li2O+ZrO2+P2O5) is 0.4 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, and / or Al2O3 / Li2O is 0.7 or less, preferably Al2O3 / Li2O is 0.6 or less, more preferably Al2O3 / Li2O is 0.5 or less, even more preferably Al2O3 / Li2O is 0.45 or less, and / or Al2O3 / (P2O5+ZrO2) is 0.1 to 0.6, and / or (ZrO2+Li2O) / Al2O3 is 3.0 to 20.0.

[0023] (16) The crystallized glass product according to any one of (2), (4) to (11), wherein the composition, in mass percent, is 58-78% SiO2, preferably 60-76% SiO2, and / or 0.1-8% Al2O3, preferably 0.5-7% Al2O3, and / or 9-22% Li2O, preferably 10-20% Li2O, and / or 6-12% ZrO2, preferably 7-12% ZrO2, and / or 1.5-7% P2O5, preferably 2-6% P2O5, and / or 0-4% K2O, preferably 0-2% K2O, and / or 0-2% MgO, preferably 0-1% MgO, and / or the glass-ceramics containing 0-2% ZnO, preferably 0-1% ZnO, and / or 0-4% Na2O, preferably 0.5-3% Na2O, and / or 0-2% SrO, preferably 0-1% SrO, and / or 0-2% BaO, preferably 0-1% BaO, and / or 0-2% CaO, preferably 0-1% CaO, and / or 0-2% TiO2, preferably 0-1% TiO2, and / or 0-3% B2O3, preferably 0-2% B2O3, and / or 0-4% Y2O3, preferably 0-2% Y2O3, and / or 0-1%, preferably 0-0.5% of a fining agent.

[0024] (17) The crystallized glass according to any one of (1) to (11) above, wherein the composition, in mass percent, of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 is 0 to 5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 is 0 to 2%, and more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 is 0 to 1%.

[0025] (18) The crystallized glass product according to any one of (1) to (11) above, wherein the composition does not contain SrO and / or does not contain BaO and / or does not contain MgO and / or does not contain CaO and / or does not contain ZnO and / or does not contain PbO and / or does not contain As2O3 and / or does not contain TiO2 and / or does not contain B2O3 and / or does not contain Y2O3 and / or does not contain F.

[0026] (19) The crystallized glass product according to any one of (1) to (11), wherein the crystal phase comprises a lithium silicate crystal phase, and / or a lithium phosphate crystal phase, and / or a petalite crystal phase, and / or a quartz solid solution crystal phase.

[0027] (20) The crystallized glass product according to any one of (1) to (11), wherein the crystal phase contains a lithium silicate crystal phase, and the lithium silicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is preferably 10 to 70%, more preferably 10 to 65%, even more preferably 15 to 60%, and most preferably 20 to 55%.

[0028] (21) The crystallized glass product according to any one of (1) to (11), wherein the crystal phase contains a lithium silicate crystal phase, the lithium silicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is preferably 30 to 65%, more preferably 35 to 60%, and even more preferably 40 to 55%.

[0029] (22) A crystallized glass product according to any one of (1) to (11), comprising a crystallized glass product containing a lithium disilicate crystal phase, wherein the lithium disilicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium disilicate crystal phase in the crystallized glass is preferably 10 to 60%, more preferably 15 to 50%, and even more preferably 20 to 45%.

[0030] (23) The crystallized glass product according to any one of (1) to (11) above, which contains a lithium phosphate crystal phase, and the mass percentage of the lithium phosphate crystal phase in the crystallized glass is 10% or less, preferably 5% or less.

[0031] (24) The crystallized glass product according to any one of (1) to (11), comprising a quartz solid solution crystal phase, the mass percentage of the quartz solid solution crystal phase in the crystallized glass product being 10% or less, preferably 5% or less.

[0032] (25) The crystallized glass product according to any one of (1) to (11), which contains a petalite crystal phase, and the mass percentage of the petalite crystal phase in the crystallized glass is 18% or less, preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less.

[0033] (26) The crystallized glass product according to any one of (1) to (11) above, wherein the four-point bending strength is 600 MPa or more, preferably 650 MPa or more, more preferably 700 MPa or more, and / or the depth of the ion exchange layer is 20 μm or more, preferably 30 μm or more, more preferably 40 μm or more, and / or the height of a falling ball impact test is 1400 mm or more, preferably 1500 mm or more, more preferably 1600 mm or more, and / or the fracture toughness is 1 MPa m 1 / 2 More than 1.3MPa m, preferably 1.3MPa m 1 / 2 More preferably, 1.5 MPa m 1 / 2 and / or Vickers hardness is 730kgf / mm 2 More than 750kgf / mm 2 More preferably, 780kgf / mm 2 and / or a dielectric constant ε r The crystallized glass product has a dielectric loss tan δ of 5.4 or more, preferably 5.8 or more, more preferably 6.0 or more, and / or a dielectric loss tan δ of 0.05 or less, preferably 0.04 or less, more preferably 0.02 or less, more preferably 0.01 or less.

[0034] (27) The crystallized glass product according to any one of (1) to (11) above, wherein the crystallization degree is 50% or more, preferably 60% or more, more preferably 70% or more, and / or the crystal grain size is 80 nm or less, preferably 50 nm or less, more preferably 30 nm or less.

[0035] (28) The crystallized glass product according to any one of (1) to (11), characterized in that the haze of the crystallized glass product having a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less, and / or the crystallized glass product having an average light transmittance at a wavelength of 400 to 800 nm of 87% or more, preferably 89% or more, more preferably 90% or more, and / or an light transmittance at a wavelength of 550 nm of 88% or more, preferably 90% or more, more preferably 91% or more, and / or an average light |B| value at 400 to 800 nm of 0.9 or less, preferably 0.8 or less, more preferably 0.7 or less.

[0036] (29) The crystallized glass product according to (28) above, which has a thickness of 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0037] (30) The crystallized glass product according to any one of (1) to (11), further comprising a colorant.

[0038] (31) The crystallized glass product according to (30), wherein the colorant contains, by mass percent, 0-4% NiO, and / or 0-4% Ni2O3; and / or 0-2% CoO, and / or 0-2% Co2O3; and / or 0-7% Fe2O3; and / or 0-4% MnO2, and / or 0-8% Er2O3; and / or 0-8% Nd2O3; and / or 0-4% Cu2O, and / or 0-8% Pr2O3; and / or 0-4% CeO2.

[0039] (32) The crystallized glass product according to (30), wherein the colorant contains, by mass percent, 0.1 to 4% of a NiO component, and / or 0.1 to 4% of a Ni2O3 component, and / or 0.05 to 2% of a CoO component, and / or 0.05 to 2% of a Co2O3 component, and / or 0.2 to 7% of a Fe2O3 component, and / or 0.1 to 4% of a MnO2 component, and / or 0.4 to 8% of a Er2O3 component, and / or 0.4 to 8% of a Nd2O3 component, and / or 0.5 to 4% of a Cu2O component, and / or 0.4 to 8% of a Pr2O3 component, and / or 0.5 to 4% of a CeO2 component.

[0040] (33) The crystallized glass product according to (30) above, wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component, and / or 0.1 to 3% of a Ni2O3 component, and / or 0.05 to 1.8% of a CoO component, and / or 0.05 to 1.8% of a Co2O3 component, and / or 0.2 to 5% of a Fe2O3 component, and / or 0.1 to 3% of a MnO2 component, and / or 0.4 to 6% of a Er2O3 component, and / or 0.4 to 6% of a Nd2O3 component, and / or 0.5 to 3% of a Cu2O component, and / or 0.4 to 6% of a Pr2O3 component, and / or 0.5 to 3% of a CeO2 component.

[0041] (34) The crystallized glass product according to (30) above, wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component and / or 0.1 to 3% of a Ni2O3 component.

[0042] (35) The crystallized glass product according to (30) above, wherein the colorant contains, by mass percent, 0.05 to 1.8% of a CoO component and / or 0.05 to 1.8% of a Co2O3 component.

[0043] (36) The crystallized glass product according to (30) above, wherein the colorant contains, by mass percent, 0.5 to 3% of a Cu2O component and / or 0.5 to 3% of a CeO2 component.

[0044] (37) The crystallized glass product according to (30), wherein the colorant contains, by mass percent, 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a CoO component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a Co2O3 component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a CoO component, 0.1 to 1% of a NiO component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a Co2O3 component, and 0.1 to 1% of a NiO component.

[0045] (38) The crystallized glass product according to (30) above, wherein the colorant contains, by mass percent, 0.4 to 6% of a Pr2O3 component, or 0.2 to 5% of an Fe2O3 component, or 0.1 to 3% of an MnO2 component, or 0.4 to 6% of an Er2O3 component, or 0.4 to 6% of an Nd2O3 component.

[0046] (39) The crystallized glass product according to (30) above, wherein the colorant contains, by mass percent, 0.4 to 6% of an Er2O3 component, 0.4 to 4% of an Nd2O3 component, and 0.1 to 2% of an MnO2 component.

[0047] (40) Crystallized glass having a composition, in mass percent, of SiO2 component of 65 to 80%, Al2O3 component of less than 5%, Li2O component of 10 to 25%, ZrO2 component of 5 to 15%, and P2O5 component of 1 to 8%.

[0048] (41) Crystallized glass having a composition, in mass percent, of SiO2 component of 55 to 80%, Al2O3 component of less than 10%, Li2O component of 8 to 25%, ZrO2 component of 5 to 15%, and P2O5 component of 1 to 8%.

[0049] (42) The crystallized glass according to (40) or (41), the composition of which contains, in mass percent, 0-5% of a K2O component, and / or 0-3% of an MgO component, and / or 0-3% of a ZnO component, and / or 0-6% of a Na2O component, and / or 0-5% of an SrO component, and / or 0-5% of a BaO component, and / or 0-5% of a CaO component, and / or 0-5% of a TiO2 component, and / or 0-5% of a B2O3 component, and / or 0-6% of a Y2O3 component, and / or 0-2% of a fining agent component.

[0050] (43) A crystallized glass containing SiO2, Al2O3, Li2O, ZrO2 and P2O5 as components, the crystallized glass containing a lithium silicate crystal phase, the lithium silicate crystal phase having a higher mass percentage than other crystal phases.

[0051] (44) Crystallized glass containing SiO2, Al2O3, Li2O, ZrO2 and P2O5 as its components, the crystallized glass having a thickness of 1 mm or less and an average light |B| value of 0.9 or less at 400 to 800 nm.

[0052] (45) Crystallized glass containing a lithium silicate crystal phase, the crystallized glass having a falling ball height of 1700 mm or more.

[0053] (46) Crystallized glass containing SiO2, Al2O3, Li2O, ZrO2 and P2O5 in its composition, wherein Al2O3 / (P2O5+ZrO2) is 1.2 or less by mass percent, the crystallized glass contains a lithium silicate crystal phase, and the falling ball height of the glass body is 1700 mm or more.

[0054] (47) A crystallized glass containing SiO2, Li2O, ZrO2 and P2O5 in its composition, the SiO2 / ZrO2 ratio being 4.0 to 15.8 by mass percent, the glass containing a lithium silicate crystal phase and having a higher mass percent than other crystal phases.

[0055] (48) The crystallized glass according to any one of (43) to (47), characterized in that its composition contains, in mass percent, 55 to 80% of a SiO2 component, and / or 8 to 25% of a Li2O component, and / or 5 to 15% of a ZrO2 component, and / or 1 to 8% of a P2O5 component.

[0056] (49) A crystallized glass containing a lithium silicate crystal phase, the crystallized glass having a composition, by mass percent, of 55 to 80% of an SiO2 component, 8 to 25% of a Li2O component, 5 to 15% of a ZrO2 component, and 1 to 8% of a P2O5 component.

[0057] (50) The crystallized glass according to any one of (43) to (49), the crystallized glass having a composition, in mass percent, of less than 10% Al2O3 component, and / or 0 to 5% K2O component, and / or 0 to 3% MgO component, and / or 0 to 3% ZnO component, and / or 0 to 6% Na2O component, and / or 0 to 5% SrO component, and / or 0 to 5% BaO component, and / or 0 to 5% CaO component, and / or 0 to 5% TiO2 component, and / or 0 to 5% B2O3 component, and / or 0 to 6% Y2O3 component, and / or 0 to 2% fining agent component.

[0058] (51) The crystallized glass according to any one of (40) to (50), the composition of which satisfies, in mass percent, one or more of the following ten conditions: 1) Al2O3 / (P2O5+ZrO2) is 1.2 or less, preferably Al2O3 / (P2O5+ZrO2) is 1.0 or less, and more preferably Al2O3 / (P2O5+ZrO2) is 0.05 to 0.7. 2) SiO2 / ZrO2 is 4.0 to 15.8, preferably SiO2 / ZrO2 is 4.5 to 12.0, more preferably SiO2 / ZrO2 is 5.0 to 9.5, and further preferably SiO2 / ZrO2 is 6.0 to 9.0. 3) P2O5+ZrO2 is 6 to 21%, preferably P2O5+ZrO2 is 7 to 18%, more preferably P2O5+ZrO2 is 8 to 16%, and further preferably P2O5+ZrO2 is 10 to 16%. 4) SiO2 / (P2O5+ZrO2) is 2.5 to 12.0, preferably SiO2 / (P2O5+ZrO2) is 3.0 to 10.0, more preferably SiO2 / (P2O5+ZrO2) is 3.5 to 7.5, and even more preferably SiO2 / (P2O5+ZrO2) is 4.0 to 6.5. 5) (ZrO2+Li2O) / Al2O3 is 2.0 or more, preferably (ZrO2+Li2O) / Al2O3 is 2.5 or more, and more preferably (ZrO2+Li2O) / Al2O3 is 2.5 to 30.0. 6) (SiO2+Al2O3) / ZrO2 is 4.0 to 16.0, preferably (SiO2+Al2O3) / ZrO2 is 4.5 to 12.0, more preferably (SiO2+Al2O3) / ZrO2 is 5.0 to 10.0, and even more preferably (SiO2+Al2O3) / ZrO2 is 6.0 to 9.5. 7) (Li2O+ZrO2) / SiO2 is 0.19 to 0.55, preferably (Li2O+ZrO2) / SiO2 is 0.2 to 0.5, more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.45, and even more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.4. 8) (MgO+ZnO) / ZrO2 is 0.65 or less, preferably (MgO+ZnO) / ZrO2 is 0.4 or less, more preferably (MgO+ZnO) / ZrO2 is 0.2 or less, and even more preferably (MgO+ZnO) / ZrO2 is 0.1 or less. 9) (Li2O+Al2O3) / ZrO2 is 0.8 to 5.0, preferably (Li2O+Al2O3) / ZrO2 is 1.0 to 4.0, more preferably (Li2O+Al2O3) / ZrO2 is 1.2 to 3.0, and even more preferably (Li2O+Al2O3) / ZrO2 is 1.5 to 2.5. 10) Li2O / (ZrO2+P2O5) is 0.5 to 3.0, preferably Li2O / (ZrO2+P2O5) is 0.6 to 2.5, more preferably Li2O / (ZrO2+P2O5) is 0.7 to 2.0, and even more preferably Li2O / (ZrO2+P2O5) is 0.8 to 1.5.

[0059] (52) The glass-ceramics according to any one of (40) to (50), wherein the composition, in mass percent, of Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.2, even more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.1, and / or Al2O3 / Li2O is 0.4 or less, preferably Al2O3 / Li2O is 0.3 or less, more preferably Al2O3 / Li2O is 0.2 or less, even more preferably Al2O3 / Li2O is 0.1 or less.

[0060] (53) The crystallized glass according to any one of (40) to (50), having a composition, in mass percent, of 68 to 78% SiO2 component, preferably 70 to 76% SiO2 component, and / or 0.1 to 4.5% Al2O3 component, preferably 0.5 to 3% Al2O3 component, and / or 12.5 to 22% Li2O component, preferably 12.5 to 20% Li2O component, and / or 6 to 12% ZrO2 component, preferably 7 to 12% ZrO2 component, and / or 1.5 to 7% P2O5 component, preferably 2 to 6% P2O5 component, and / or 0 to 4% K2O component, preferably 0 to 2% K2O component, and / or 0 to 2% MgO component, preferably 0 to 1% MgO component, and / or ZnO component. the glass-ceramics containing 0-2% of a ZnO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0061] (54) The crystallized glass according to any one of (41), (43) to (50), wherein the composition, in mass percent, of Al2O3 / (Li2O+ZrO2+P2O5) is 0.4 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, and / or Al2O3 / Li2O is 0.7 or less, preferably Al2O3 / Li2O is 0.6 or less, more preferably Al2O3 / Li2O is 0.5 or less, even more preferably Al2O3 / Li2O is 0.45 or less, and / or Al2O3 / (P2O5+ZrO2) is 0.1 to 0.6, and / or (ZrO2+Li2O) / Al2O3 is 3.0 to 20.0.

[0062] (55) The crystallized glass according to any one of (41), (43) to (50), having a composition, in mass percent, of 58 to 78% SiO2 component, preferably 60 to 76% SiO2 component, and / or 0.1 to 8% Al2O3 component, preferably 0.5 to 7% Al2O3 component, and / or 9 to 22% Li2O component, preferably 10 to 20% Li2O component, and / or 6 to 12% ZrO2 component, preferably 7 to 12% ZrO2 component, and / or 1.5 to 7% P2O5 component, preferably 2 to 6% P2O5 component, and / or 0 to 4% K2O component, preferably 0 to 2% K2O component, and / or 0 to 2% MgO component, preferably 0 to 1% MgO component, and / or ZnO component. the glass-ceramics containing 0-2% of a ZnO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0063] (56) The crystallized glass according to any one of (40) to (50), the crystallized glass having a composition, in mass percent, of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components in the range of 0 to 5%, preferably of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components in the range of 0 to 2%, more preferably of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components in the range of 0 to 1%.

[0064] (57) Crystallized glass according to any one of (40) to (50), wherein the composition does not contain SrO, and / or does not contain BaO, and / or does not contain MgO, and / or does not contain CaO, and / or does not contain ZnO, and / or does not contain PbO, and / or does not contain As2O3, and / or does not contain TiO2, and / or does not contain B2O3, and / or does not contain Y2O3, and / or does not contain F.

[0065] (58) The crystallized glass according to any one of (40) to (50), wherein the crystal phase includes a lithium silicate crystal phase, and / or a lithium phosphate crystal phase, and / or a petalite crystal phase, and / or a quartz solid solution crystal phase.

[0066] (59) The crystallized glass according to any one of (40) to (50), wherein the crystal phase contains a lithium silicate crystal phase, the lithium silicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is preferably 10 to 70%, more preferably 10 to 65%, even more preferably 15 to 60%, and most preferably 20 to 55%.

[0067] (60) The crystallized glass according to any one of (40) to (50), wherein the crystal phase contains a lithium silicate crystal phase, the lithium silicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is preferably 30 to 65%, more preferably 35 to 60%, and even more preferably 40 to 55%.

[0068] (61) The crystallized glass according to any one of (40) to (50), wherein the crystal phase contains a lithium disilicate crystal phase, the lithium disilicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium disilicate crystal phase in the crystallized glass is preferably 10 to 60%, more preferably 15 to 50%, and even more preferably 20 to 45%.

[0069] (62) The crystallized glass according to any one of (40) to (50), which contains a lithium phosphate crystal phase, and the mass percentage of the lithium phosphate crystal phase in the crystallized glass is 10% or less, preferably 5% or less.

[0070] (63) The crystallized glass according to any one of (40) to (50), which contains a quartz solid solution crystal phase, and the mass percentage of the quartz solid solution crystal phase in the crystallized glass is 10% or less, preferably 5% or less.

[0071] (64) The crystallized glass according to any one of (40) to (50), which contains a petalite crystal phase, and the mass percentage of the petalite crystal phase in the crystallized glass is 18% or less, preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.

[0072] (65) The crystallized glass according to any one of (40) to (50), wherein the crystallinity is 50% or more, preferably 60% or more, more preferably 70% or more, and / or the crystal grain size is 80 nm or less, preferably 50 nm or less, more preferably 30 nm or less, and / or the thermal expansion coefficient is 70×10 -7 / K~90×10 -7 / K, and / or the refractive index is 1.5520 to 1.5700.

[0073] (66) The crystallized glass according to any one of (40) to (50), wherein the drop height of the glass body is 1700 mm or more, preferably 1900 mm or more, more preferably 2000 mm or more, and / or the Vickers hardness is 630 kgf / mm 2 More than 650kgf / mm 2 More preferably, 680kgf / mm 2 and / or a relative dielectric constant of 5.4 or more, preferably 5.8 or more, more preferably 6.0 or more, and / or a dielectric loss of 0.05 or less, preferably 0.04 or less, more preferably 0.03 or less, more preferably 0.01 or less, and / or a surface resistance of 1×10 9 Ω cm or more, preferably 1×10 10 Ω cm or more, more preferably 1×10 11 The crystallized glass has a resistivity of Ω·cm or more.

[0074] (67) The glass-ceramics according to any one of (40) to (50), wherein the haze of the glass-ceramics having a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less, and / or the average light transmittance at a wavelength of 400 to 800 nm is 87% or more, preferably 89% or more, more preferably 90% or more, and / or the light transmittance at a wavelength of 550 nm is 88% or more, preferably 90% or more, more preferably 91% or more, and / or the average light |B| value at 400 to 800 nm is 0.9 or less, preferably 0.8 or less, more preferably 0.7 or less.

[0075] (68) The crystallized glass according to (67), wherein the thickness of the crystallized glass is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0076] (69) The crystallized glass according to any one of (40) to (50), which contains a colorant.

[0077] (70) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0 to 4% of a NiO component, and / or 0 to 4% of a Ni2O3 component, and / or 0 to 2% of a CoO component, and / or 0 to 2% of a Co2O3 component, and / or 0 to 7% of a Fe2O3 component, and / or 0 to 4% of a MnO2 component, and / or 0 to 8% of a Er2O3 component, and / or 0 to 8% of a Nd2O3 component, and / or 0 to 4% of a Cu2O component, and / or 0 to 8% of a Pr2O3 component, and / or 0 to 4% of a CeO2 component.

[0078] (71) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.1 to 4% of a NiO component, and / or 0.1 to 4% of a Ni2O3 component, and / or 0.05 to 2% of a CoO component, and / or 0.05 to 2% of a Co2O3 component, and / or 0.2 to 7% of a Fe2O3 component, and / or 0.1 to 4% of a MnO2 component, and / or 0.4 to 8% of a Er2O3 component, and / or 0.4 to 8% of a Nd2O3 component, and / or 0.5 to 4% of a Cu2O component, and / or 0.4 to 8% of a Pr2O3 component, and / or 0.5 to 4% of a CeO2 component.

[0079] (72) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component, and / or 0.1 to 3% of a Ni2O3 component, and / or 0.05 to 1.8% of a CoO component, and / or 0.05 to 1.8% of a Co2O3 component, and / or 0.2 to 5% of a Fe2O3 component, and / or 0.1 to 3% of a MnO2 component, and / or 0.4 to 6% of a Er2O3 component, and / or 0.4 to 6% of a Nd2O3 component, and / or 0.5 to 3% of a Cu2O component, and / or 0.4 to 6% of a Pr2O3 component, and / or 0.5 to 3% of a CeO2 component.

[0080] (73) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component and / or 0.1 to 3% of a Ni2O3 component.

[0081] (74) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.05 to 1.8% of a CoO component and / or 0.05 to 1.8% of a Co2O3 component.

[0082] (75) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.5 to 3% of a Cu2O component and / or 0.5 to 3% of a CeO2 component.

[0083] (76) The crystallized glass according to (69), wherein the colorant contains 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a CoO component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a Co2O3 component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a CoO component, 0.1 to 1% of a NiO component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a Co2O3 component, and 0.1 to 1% of a NiO component.

[0084] (77) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.4 to 6% of a Pr2O3 component, or 0.2 to 5% of an Fe2O3 component, or 0.1 to 3% of an MnO2 component, or 0.4 to 6% of an Er2O3 component, or 0.4 to 6% of an Nd2O3 component.

[0085] (78) The crystallized glass according to (69), wherein the colorant contains, by mass percent, 0.4 to 6% of an Er2O3 component, 0.4 to 4% of an Nd2O3 component, and 0.1 to 2% of an MnO2 component.

[0086] (79) A glass composition, the composition of which is expressed in mass percent, contains 65 to 80% of a SiO2 component, less than 5% of an Al2O3 component, 10 to 25% of a Li2O component, 5 to 15% of a ZrO2 component, and 1 to 8% of a P2O5 component.

[0087] (80) A glass composition, the composition of which is expressed in mass percent, contains 55 to 80% of a SiO2 component, less than 10% of an Al2O3 component, 8 to 25% of a Li2O component, 5 to 15% of a ZrO2 component, and 1 to 8% of a P2O5 component.

[0088] (81) A glass composition containing SiO2, Al2O3, Li2O, ZrO2 and P2O5 as components, the composition being expressed in mass percent, Al2O3 / (P2O5+ZrO2) being 1.2 or less, and the thermal expansion coefficient being 65×10 -7 / K~79×10 -7 / K.

[0089] (82) A glass composition, characterized in that the composition contains SiO2, Li2O, ZrO2 and P2O5 as components, the composition is expressed in mass percent, and SiO2 / ZrO2 is 4.0 to 15.8.

[0090] (83) The glass composition according to (81) or (82), which contains, by mass percent, 55 to 80% of a SiO2 component, and / or less than 10% of an Al2O3 component, and / or 8 to 25% of a Li2O component, and / or 5 to 15% of a ZrO2 component, and / or 1 to 8% of a P2O5 component.

[0091] (84) The glass composition according to any one of (79) to (83), comprising, by mass percent, 0 to 5% of a K2O component, and / or 0 to 3% of an MgO component, and / or 0 to 3% of a ZnO component, and / or 0 to 6% of a Na2O component, and / or 0 to 5% of a SrO component, and / or 0 to 5% of a BaO component, and / or 0 to 5% of a CaO component, and / or 0 to 5% of a TiO2 component, and / or 0 to 5% of a B2O3 component, and / or 0 to 6% of a Y2O3 component, and / or 0 to 2% of a fining agent component.

[0092] (85) The glass composition according to any one of (79) to (83), which satisfies, in mass percent, one or more of the following ten conditions: 1) Al2O3 / (P2O5+ZrO2) is 1.2 or less, preferably Al2O3 / (P2O5+ZrO2) is 1.0 or less, and more preferably Al2O3 / (P2O5+ZrO2) is 0.05 to 0.7. 2) SiO2 / ZrO2 is 4.0 to 15.8, preferably SiO2 / ZrO2 is 4.5 to 12.0, more preferably SiO2 / ZrO2 is 5.0 to 9.5, and further preferably SiO2 / ZrO2 is 6.0 to 9.0. 3) P2O5+ZrO2 is 6 to 21%, preferably P2O5+ZrO2 is 7 to 18%, more preferably P2O5+ZrO2 is 8 to 16%, and further preferably P2O5+ZrO2 is 10 to 16%. 4) SiO2 / (P2O5+ZrO2) is 2.5 to 12.0, preferably SiO2 / (P2O5+ZrO2) is 3.0 to 10.0, more preferably SiO2 / (P2O5+ZrO2) is 3.5 to 7.5, and further preferably SiO2 / (P2O5+ZrO2) is 4.0 to 6.5. 5) (ZrO2+Li2O) / Al2O3 is 2.0 or more, preferably (ZrO2+Li2O) / Al2O3 is 2.5 or more, and more preferably (ZrO2+Li2O) / Al2O3 is 2.5 to 30.0. 6) (SiO2+Al2O3) / ZrO2 is 4.0 to 16.0, preferably (SiO2+Al2O3) / ZrO2 is 4.5 to 12.0, more preferably (SiO2+Al2O3) / ZrO2 is 5.0 to 10.0, and further preferably (SiO2+Al2O3) / ZrO2 is 6.0 to 9.5. 7) (Li2O+ZrO2) / SiO2 is 0.19 to 0.55, preferably (Li2O+ZrO2) / SiO2 is 0.2 to 0.5, more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.45, and further preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.4. 8) (MgO+ZnO) / ZrO2 is 0.65 or less, preferably (MgO+ZnO) / ZrO2 is 0.4 or less, more preferably (MgO+ZnO) / ZrO2 is 0.2 or less, and even more preferably (MgO+ZnO) / ZrO2 is 0.1 or less. 9) (Li2O+Al2O3) / ZrO2 is 0.8 to 5.0, preferably (Li2O+Al2O3) / ZrO2 is 1.0 to 4.0, more preferably (Li2O+Al2O3) / ZrO2 is 1.2 to 3.0, and even more preferably (Li2O+Al2O3) / ZrO2 is 1.5 to 2.5. 10) Li2O / (ZrO2+P2O5) is 0.5 to 3.0, preferably Li2O / (ZrO2+P2O5) is 0.6 to 2.5, more preferably Li2O / (ZrO2+P2O5) is 0.7 to 2.0, and even more preferably Li2O / (ZrO2+P2O5) is 0.8 to 1.5.

[0093] (86) The glass composition according to any one of (79) to (83), comprising, in mass percent, Al2O3 / (Li2O+ZrO2+P2O5) of 0.3 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) of 0.25 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) of 0.01 to 0.2, even more preferably Al2O3 / (Li2O+ZrO2+P2O5) of 0.01 to 0.1, and / or Al2O3 / Li2O of 0.4 or less, preferably Al2O3 / Li2O of 0.3 or less, more preferably Al2O3 / Li2O of 0.2 or less, even more preferably Al2O3 / Li2O of 0.1 or less.

[0094] (87) The glass composition according to any one of (79) to (83), wherein the composition is, in mass percent, 68 to 78% of a SiO2 component, preferably 70 to 76% of a SiO2 component, and / or 0.1 to 4.5% of an Al2O3 component, preferably 0.5 to 3% of an Al2O3 component, and / or 12.5 to 22% of a Li2O component, preferably 12.5 to 20% of a Li2O component, and / or 6 to 12% of a ZrO2 component, preferably 7 to 12% of a ZrO2 component, and / or 1.5 to 7% of a P2O5 component, preferably 2 to 6% of a P2O5 component, and / or 0 to 4% of a K2O component, preferably 0 to 2% of a K2O component, and / or 0 to 2% of a MgO component, preferably 0 to 1% of a MgO component, and / or Z The composition contains 0-2% of an nO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0095] (88) The glass composition according to any one of (80) to (83), wherein the composition contains, in mass percent, Al2O3 / (Li2O+ZrO2+P2O5) is 0.4 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, and / or Al2O3 / Li2O is 0.7 or less, preferably Al2O3 / Li2O is 0.6 or less, more preferably Al2O3 / Li2O is 0.5 or less, even more preferably Al2O3 / Li2O is 0.45 or less, and / or Al2O3 / (P2O5+ZrO2) is 0.1 to 0.6, and / or (ZrO2+Li2O) / Al2O3 is 3.0 to 20.0.

[0096] (89) The glass composition according to any one of (80) to (83), comprising, in mass percent, 58 to 78% of a SiO2 component, preferably 60 to 76% of a SiO2 component, and / or 0.1 to 8% of an Al2O3 component, preferably 0.5 to 7% of an Al2O3 component, and / or 9 to 22% of a Li2O component, preferably 10 to 20% of a Li2O component, and / or 6 to 12% of a ZrO2 component, preferably 7 to 12% of a ZrO2 component, and / or 1.5 to 7% of a P2O5 component, preferably 2 to 6% of a P2O5 component, and / or 0 to 4% of a K2O component, preferably 0 to 2% of a K2O component, and / or 0 to 2% of a MgO component, preferably 0 to 1% of a MgO component, and / or ZnO component. and / or 0-2% of a ZnO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0097] (90) A glass composition according to any one of (79) to (83), which contains, by mass percent, 0 to 5% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components, preferably 0 to 2% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components, and more preferably 0 to 1% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components.

[0098] (91) A glass composition according to any one of (79) to (83), wherein the composition does not contain SrO, and / or does not contain BaO; and / or does not contain MgO; and / or does not contain CaO, and / or does not contain ZnO; and / or does not contain PbO; and / or does not contain As2O3; and / or does not contain TiO2; and / or does not contain B2O3; and / or does not contain Y2O3; and / or does not contain F.

[0099] (92) The glass composition according to any one of (79) to (83), wherein the thermal expansion coefficient is 65×10 -7 / K~80×10 -7 / K, and / or the refractive index is 1.5400 to 1.5600.

[0100] (93) The glass composition according to any one of (79) to (83), further comprising a colorant.

[0101] (94) The glass composition according to (93), comprising, in mass percent, 0-4% NiO, 0-4% Ni2O3, 0-2% CoO, 0-2% Co2O3, 0-7% Fe2O3, 0-4% MnO2, 0-8% Er2O3, 0-8% Nd2O3, 0-4% Cu2O, 0-8% Pr2O3, and / or 0-4% CeO2.

[0102] (95) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.1 to 4% of a NiO component, and / or 0.1 to 4% of a Ni2O3 component, and / or 0.05 to 2% of a CoO component, and / or 0.05 to 2% of a Co2O3 component, and / or 0.2 to 7% of a Fe2O3 component, and / or 0.1 to 4% of a MnO2 component, and / or 0.4 to 8% of a Er2O3 component, and / or 0.4 to 8% of a Nd2O3 component, and / or 0.5 to 4% of a Cu2O component, and / or 0.4 to 8% of a Pr2O3 component, and / or 0.5 to 4% of a CeO2 component.

[0103] (96) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component, and / or 0.1 to 3% of a Ni2O3 component, and / or 0.05 to 1.8% of a CoO component, and / or 0.05 to 1.8% of a Co2O3 component, and / or 0.2 to 5% of a Fe2O3 component, and / or 0.1 to 3% of a MnO2 component, and / or 0.4 to 6% of a Er2O3 component, and / or 0.4 to 6% of a Nd2O3 component, and / or 0.5 to 3% of a Cu2O component, and / or 0.4 to 6% of a Pr2O3 component, and / or 0.5 to 3% of a CeO2 component.

[0104] (97) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component and / or 0.1 to 3% of a Ni2O3 component.

[0105] (98) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.05 to 1.8% of a CoO component and / or 0.05 to 1.8% of a Co2O3 component.

[0106] (99) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.5 to 3% of a Cu2O component and / or 0.5 to 3% of a CeO2 component.

[0107] (100) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a CoO component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a Co2O3 component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a CoO component, 0.1 to 1% of a NiO component, or 0.2 to 5% of an Fe2O3 component, 0.05 to 0.3% of a Co2O3 component, and 0.1 to 1% of a NiO component.

[0108] (101) The glass composition according to (93), wherein the colorant contains, by mass percent, 0.4 to 6% of a Pr2O3 component, or 0.2 to 5% of an Fe2O3 component, or 0.1 to 3% of an MnO2 component, or 0.4 to 6% of an Er2O3 component, or 0.4 to 6% of an Nd2O3 component.

[0109] (102) (93) The glass composition according to the present invention, wherein the colorant contains, by mass percent, 0.4 to 6% of an Er2O3 component, 0.4 to 4% of an Nd2O3 component, and 0.1 to 2% of an MnO2 component.

[0110] (103) A crystallized glass-molded article comprising the crystallized glass according to any one of (40) to (78).

[0111] (104) A glass cover comprising a crystallized glass cover according to any one of (1) to (39), and / or a crystallized glass according to any one of (40) to (78), and / or a glass composition according to any one of (79) to (102), and / or a crystallized glass molded body according to (103).

[0112] (105) A glass part comprising a crystallized glass product according to any one of (1) to (39), and / or a crystallized glass product according to any one of (40) to (78), and / or a glass composition according to any one of (79) to (102), and / or a crystallized glass molded body according to (103).

[0113] (106) A display device comprising a crystallized glass product according to any one of (1) to (39), and / or a crystallized glass according to any one of (40) to (78), and / or a glass composition according to any one of (79) to (102), and / or a crystallized glass molded body according to (103), and / or a glass cover according to (104), and / or a glass part according to (105).

[0114] (107) An electronic device comprising a crystallized glass product according to any one of (1) to (39), and / or a crystallized glass according to any one of (40) to (78), and / or a glass composition according to any one of (79) to (102), and / or a crystallized glass molded body according to (103), and / or a glass cover according to (104), and / or a glass part according to (105).

[0115] (108) A method for forming a glass composition, a method for forming crystallized glass from the glass composition by a crystallization method, and a method for forming a crystallized glass product from the crystallized glass by a chemical strengthening method, wherein the crystallized glass product has a composition, in mass percent, of SiO2 component: 65 to 80%; Al2O3 component: less than 5%; Li2O component: 10 to 25%; ZrO2 component: 5 to 15%; and P2O5 component: 1 to 8%.

[0116] (109) A method for forming a glass composition, a method for forming a crystallized glass from the glass composition by a crystallization method, and a method for forming a crystallized glass product from the crystallized glass by a chemical strengthening method, wherein the crystallized glass product contains, in mass percent, 55 to 80% SiO2, less than 10% Al2O3, 8 to 25% Li2O, 5 to 15% ZrO2, and 1 to 8% P2O5.

[0117] (110) A method for producing a vitrified crystallized glass product, comprising: a method for forming a glass composition; a method for forming a crystallized glass from the glass composition by a crystallization method; and a method for forming a crystallized glass product from the crystallized glass by a chemical strengthening method, wherein the crystallized glass product has an Al2O3 / (P2O5+ZrO2) ratio of 1.2 or less.

[0118] (111) A method for forming a glass composition, a method for crystallizing the glass composition by a crystallization method, and a method for forming a crystallized vitrified product by a chemical strengthening method after the crystallization, the crystallized vitrified product including a lithium silicate crystal phase having a higher mass percentage than other crystal phases.

[0119] (112) A method for producing crystallized glass according to (110) or (111), wherein the composition of the crystallized glass contains, in mass percent, 55 to 80% of a SiO2 component, and / or less than 10% of an Al2O3 component, and / or 8 to 25% of a Li2O component, and / or 5 to 15% of a ZrO2 component, and / or 1 to 8% of a P2O5 component.

[0120] (113) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the composition of the crystallized glass product contains, in mass percent, 0-5% of a K2O component, and / or 0-3% of an MgO component, and / or 0-3% of a ZnO component, and / or 0-6% of a Na2O component, and / or 0-5% of an SrO component, and / or 0-5% of a BaO component, and / or 0-5% of a CaO component, and / or 0-5% of a TiO2 component, and / or 0-5% of a B2O3 component, and / or 0-6% of a Y2O3 component, and / or 0-2% of a fining agent component.

[0121] (114) A method for producing a crystallized glass product according to any one of (108) to (113), wherein the composition of the crystallized glass product satisfies one or more of the following ten conditions in terms of mass percent: 1) Al2O3 / (P2O5+ZrO2) is 1.2 or less, preferably Al2O3 / (P2O5+ZrO2) is 1.0 or less, and more preferably Al2O3 / (P2O5+ZrO2) is 0.05 to 0.7. 2) SiO2 / ZrO2 is 4.0 to 15.8, preferably SiO2 / ZrO2 is 4.5 to 12.0, more preferably SiO2 / ZrO2 is 5.0 to 9.5, and further preferably SiO2 / ZrO2 is 6.0 to 9.0. 3) P2O5+ZrO2 is 6 to 21%, preferably P2O5+ZrO2 is 7 to 18%, more preferably P2O5+ZrO2 is 8 to 16%, and further preferably P2O5+ZrO2 is 10 to 16%. 4) SiO2 / (P2O5+ZrO2) is 2.5 to 12.0, preferably SiO2 / (P2O5+ZrO2) is 3.0 to 10.0, more preferably SiO2 / (P2O5+ZrO2) is 3.5 to 7.5, and further preferably SiO2 / (P2O5+ZrO2) is 4.0 to 6.5. 5) (ZrO2+Li2O) / Al2O3 is 2.0 or more, preferably (ZrO2+Li2O) / Al2O3 is 2.5 or more, and more preferably (ZrO2+Li2O) / Al2O3 is 2.5 to 30.0. 6) (SiO2+Al2O3) / ZrO2 is 4.0 to 16.0, preferably (SiO2+Al2O3) / ZrO2 is 4.5 to 12.0, more preferably (SiO2+Al2O3) / ZrO2 is 5.0 to 10.0, and further preferably (SiO2+Al2O3) / ZrO2 is 6.0 to 9.5. 7) (Li2O+ZrO2) / SiO2 is 0.19 to 0.55, preferably (Li2O+ZrO2) / SiO2 is 0.2 to 0.5, more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.45, and further preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.4. 8) (MgO+ZnO) / ZrO2 is 0.65 or less, preferably (MgO+ZnO) / ZrO2 is 0.4 or less, more preferably (MgO+ZnO) / ZrO2 is 0.2 or less, and even more preferably (MgO+ZnO) / ZrO2 is 0.1 or less. 9) (Li2O+Al2O3) / ZrO2 is 0.8 to 5.0, preferably (Li2O+Al2O3) / ZrO2 is 1.0 to 4.0, more preferably (Li2O+Al2O3) / ZrO2 is 1.2 to 3.0, and even more preferably (Li2O+Al2O3) / ZrO2 is 1.5 to 2.5. 10) Li2O / (ZrO2+P2O5) is 0.5 to 3.0, preferably Li2O / (ZrO2+P2O5) is 0.6 to 2.5, more preferably Li2O / (ZrO2+P2O5) is 0.7 to 2.0, and even more preferably Li2O / (ZrO2+P2O5) is 0.8 to 1.5.

[0122] (115) A method for producing crystallized glass according to any one of (108) to (112), wherein the composition of the crystallized glass product is, in mass percent, Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.2, even more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.1, and / or Al2O3 / Li2O is 0.4 or less, preferably Al2O3 / Li2O is 0.3 or less, more preferably Al2O3 / Li2O is 0.2 or less, even more preferably Al2O3 / Li2O is 0.1 or less.

[0123] (116) A method for producing crystallized glass according to any one of (108) to (112), wherein the composition of the crystallized glass is, in mass percent, 68 to 78% SiO2 component, preferably 70 to 76% SiO2 component, and / or 0.1 to 4.5% Al2O3 component, preferably 0.5 to 3% Al2O3 component, and / or 12.5 to 22% Li2O component, preferably 12.5 to 20% Li2O component, and / or 6 to 12% ZrO2 component, preferably 7 to 12% ZrO2 component, and / or 1.5 to 7% P2O5 component, preferably 2 to 6% P2O5 component, and / or 0 to 4% K2O component, preferably 0 to 2% K2O component, and / or 0 to 2% MgO component, preferably 0 to 1% MgO component. and / or 0-2% of a ZnO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0124] (117) A method for producing crystallized glass according to any one of (109) to (112), wherein the composition, in mass percent, is Al2O3 / (Li2O+ZrO2+P2O5) is 0.4 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, and / or Al2O3 / Li2O is 0.7 or less, preferably Al2O3 / Li2O is 0.6 or less, more preferably Al2O3 / Li2O is 0.5 or less, even more preferably Al2O3 / Li2O is 0.45 or less, and / or Al2O3 / (P2O5+ZrO2) is 0.1 to 0.6, and / or (ZrO2+Li2O) / Al2O3 is 3.0 to 20.0.

[0125] (118) A method for producing crystallized glass according to any one of (109) to (112), characterized in that the composition of the crystallized glass contains, in mass percent, 58-78% SiO2 component, preferably 60-76% SiO2 component, and / or 0.1-8% Al2O3 component, preferably 0.5-7% Al2O3 component, and / or 9-22% Li2O component, preferably 10-20% Li2O component, and / or 6-12% Li2O component, preferably 7-12% Li2O component, and / or 1.5-7% P2O5 component, preferably 2-6% P2O5 component, and / or 0-4% K2O component, preferably 0-2% K2O component, and / or 0-2% MgO component, preferably 0-1% MgO component. and / or 0-2% ZnO component, preferably 0-1% ZnO component, and / or 0-4% Na_2O component, preferably 0.5-3% Na2O component, and / or 0-2% SrO component, preferably 0-1% SrO component, and / or 0-2% BaO component, preferably 0-1% BaO component, and / or 0-2% CaO component, preferably 0-1% CaO component, and / or 0-2% TiO2 component, preferably 0-1% TiO2 component. and / or 0-3% B2O3 component, preferably 0-2% B2O3 component. and / or 0-4% Y2O3 component, preferably 0-2% Y2O3 component. and / or 0-1% clarifier component, preferably 0-0.5% clarifier component.

[0126] (119) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the composition of the crystallized glass product contains, in mass percent, 0 to 5% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components, preferably 0 to 2% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components, and more preferably 0 to 1% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2 components.

[0127] (120) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the composition of the crystallized glass product does not contain SrO, and / or does not contain BaO, and / or does not contain MgO, and / or does not contain CaO, and / or does not contain ZnO, and / or does not contain PbO, and / or does not contain As2O3, and / or does not contain TiO2, and / or does not contain B2O3, and / or does not contain Y2O3, and / or does not contain F.

[0128] (121) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the crystal phase contains a lithium silicate crystal phase, and / or a lithium phosphate crystal phase, and / or a petalite crystal phase, and / or a quartz solid solution crystal phase.

[0129] (122) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the crystal phase contains a lithium silicate crystal phase, and the lithium silicate crystal phase has a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is preferably 10 to 70%, more preferably 10 to 65%, even more preferably 15 to 60%, and most preferably 20 to 55%.

[0130] (123) A method for producing a crystallized glass product according to any one of (108) to (112), comprising the step of: providing a crystallized glass product comprising a crystalline phase containing a lithium silicate crystalline phase, the crystalline phase containing the lithium silicate crystalline phase having a mass percentage higher than that of other crystalline phases, preferably 30 to 65%, more preferably 35 to 60%, and even more preferably 40 to 55%.

[0131] (124) A method for producing a crystallized glass product according to any one of (108) to (112), comprising the step of: providing a crystallized glass product comprising a lithium disilicate crystal phase, the lithium disilicate crystal phase having a higher mass percentage than the other crystal phases, and the mass percentage of the lithium disilicate crystal phase in the crystallized glass is preferably 10 to 60%, more preferably 15 to 50%, and even more preferably 20 to 45%.

[0132] (125) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the crystallized glass contains a lithium phosphate crystal phase, and the mass percentage of the lithium phosphate crystal phase in the crystallized glass is 10% or less, preferably 5% or less.

[0133] (126) A method for producing a crystallized glass product according to any one of (108) to (112), comprising the steps of: containing a quartz solid solution crystal phase; and the mass percentage of the quartz solid solution crystal phase in the crystallized glass is 10% or less, preferably 5% or less.

[0134] (127) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the crystallized glass product contains a petalite crystal phase, and the mass percentage of the petalite crystal phase in the crystallized glass is 18% or less, preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less.

[0135] (128) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the crystallized glass product has a four-point bending strength of 600 MPa or more, preferably 650 MPa or more, more preferably 700 MPa or more, and / or an ion-exchange layer depth of 20 μm or more, preferably 30 μm or more, more preferably 40 μm or more, and / or a falling ball impact test height of 1400 mm or more, preferably 1500 mm or more, more preferably 1600 mm or more, and / or a fracture toughness of 1 MPa m 1 / 2 More than 1.3MPa m, preferably 1.3MPa m 1 / 2 More preferably, 1.5 MPa m 1 / 2and / or Vickers hardness is 730kgf / mm 2 More than 750kgf / mm 2 More preferably, 780kgf / mm 2 or more; and / or a relative dielectric constant of 5.4 or more, preferably 5.8 or more, more preferably 6.0 or more; and / or a dielectric loss of 0.05 or less, preferably 0.04 or less, more preferably 0.02 or less, more preferably 0.01 or less; and / or a crystallinity of 50% or more, preferably 60% or more, more preferably 70% or more; and / or a crystal grain size of 80 nm or less, preferably 50 nm or less, more preferably 30 nm or less.

[0136] (129) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the haze of the crystallized glass having a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less, and / or the average light transmittance at a wavelength of 400 to 800 nm is 87% or more, preferably 89% or more, more preferably 90% or more, and / or the light transmittance at a wavelength of 550 nm is 88% or more, preferably 90% or more, more preferably 91% or more, and / or the average light |B| value at 400 to 800 nm is 0.9 or less, preferably 0.8 or less, more preferably 0.7 or less.

[0137] (130) The method for producing crystallized glass according to (129), wherein the thickness of the crystallized glass is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0138] (131) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the colorant in the crystallized glass product contains, by mass percent, 0-4% NiO, 0-4% Ni2O3, 0-2% CoO, 0-2% Co2O3, 0-7% Fe2O3, 0-4% MnO2, 0-8% Er2O3, 0-8% Nd2O3, 0-4% Cu2O, 0-8% Pr2O3, and / or 0-4% CeO2.

[0139] (132) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.1 to 4% of a NiO component, and / or 0.1 to 4% of a Ni2O3 component, and / or 0.05 to 2% of a CoO component, and / or 0.05 to 2% of a Co2O3 component, and / or 0.2 to 7% of a Fe2O3 component, and / or 0.1 to 4% of a MnO2 component, and / or 0.4 to 8% of a Er2O3 component, and / or 0.4 to 8% of a Nd2O3 component, and / or 0.5 to 4% of a Cu2O component, and / or 0.4 to 8% of a Pr2O3 component, and / or 0.5 to 4% of a CeO2 component.

[0140] (133) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component, and / or 0.1 to 3% of a Ni2O3 component, and / or 0.05 to 1.8% of a CoO component, and / or 0.05 to 1.8% of a Co2O3 component, and / or 0.2 to 5% of a Fe2O3 component, and / or 0.1 to 3% of a MnO2 component, and / or 0.4 to 6% of a Er2O3 component, and / or 0.4 to 6% of a Nd2O3 component, and / or 0.5 to 3% of a Cu2O component, and / or 0.4 to 6% of a Pr2O3 component, and / or 0.5 to 3% of a CeO2 component.

[0141] (134) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component and / or 0.1 to 3% of a Ni2O3 component.

[0142] (135) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.05 to 1.8% of a CoO component and / or 0.05 to 1.8% of a Co2O3 component.

[0143] (136) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.5 to 3% of a Cu2O component and / or 0.5 to 3% of a CeO2 component.

[0144] (137) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.2-5% Fe2O3, 0.05-0.3% CoO, or 0.2-5% Fe2O3, 0.05-0.3% Co2O3, or 0.2-5% Fe2O3, 0.05-0.3% CoO, 0.1-1% NiO, or 0.2-5% Fe2O3, 0.05-0.3% Co2O3, and 0.1-1% NiO.

[0145] (138) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.4 to 6% of a Pr2O3 component, or 0.2 to 5% of an Fe2O3 component, or 0.1 to 3% of an MnO2 component, or 0.4 to 6% of an Er2O3 component, or 0.4 to 6% of an Nd2O3 component.

[0146] (139) A method for producing a crystallized glass product according to (131), wherein the colorant contains, by mass percent, 0.4 to 6% of an Er2O3 component, 0.4 to 4% of an Nd2O3 component, and 0.1 to 2% of an MnO2 component.

[0147] (140) A method for producing a crystallized glass product according to any one of (108) to (112), comprising a process of raising the temperature to a predetermined crystallization treatment temperature, holding the temperature for a certain period of time after the temperature has been reached, and then lowering the temperature, wherein the crystallization treatment temperature is 580 to 750°C, preferably 600 to 700°C, and the holding time at the crystallization treatment temperature is 0 to 8 hours, preferably 1 to 6 hours.

[0148] (141) A method for producing crystallized glass according to any one of (108) to (112), comprising carrying out a nucleation process at a first temperature and then carrying out a crystal growth process at a second temperature higher than the temperature of the nucleation process.

[0149] (142) A method for producing crystallized glass according to (141), wherein the crystallization method is a method in which the first temperature is 470-580°C and the second temperature is 600-750°C, and the holding time at the first temperature is 0-24 hours, preferably 2-15 hours, and the holding time at the second temperature is 0-10 hours, preferably 0.5-6 hours.

[0150] (143) A method for producing a crystallized glass product according to any one of (108) to (112), wherein the chemical strengthening method includes immersing the crystallized glass in a molten Na salt bath at 350°C to 470°C for 1 to 36 hours, preferably at 380°C to 460°C, more preferably for 2 to 24 hours, and / or immersing in a molten K salt bath at 360°C to 450°C for 1 to 36 hours, preferably at 2 to 24 hours, and / or immersing in a mixed salt bath of molten K salt and Na salt at 360°C to 450°C for 1 to 36 hours, preferably at 2 to 24 hours.

[0151] (144) A method for producing crystallized vitrified glass, comprising: a process for forming a glass composition; and a process for crystallizing and vitrifying the glass composition by a crystallization process, wherein the composition of the crystallized vitrified glass contains, in mass percent, 65-80% SiO2 component; less than 5% Al2O3 component; 10-25% Li2O component; 5-15% ZrO2 component; and 1-8% P2O5 component.

[0152] (145) A method for producing crystallized vitrified glass, comprising a process for forming a composite glass and a process for crystallizing the composite glass by a crystallization method, wherein the crystallized vitrified glass has a composition, in mass percent, of 55-80% SiO2 component; less than 10% Al2O3 component; 8-25% Li2O component; 5-15% ZrO2 component; and 1-8% P2O5 component.

[0153] (146) A method for producing crystallized glass, comprising: a process for forming a glass composition; and a process for forming crystallized glass from the glass composition by a crystallization process, wherein the crystallized glass has a mass percent of Al2O3 / (P2O5+ZrO2) of 1.2 or less.

[0154] (147) A method for producing crystallized vitrified glass, comprising: a process for forming a glass composition; and a process for crystallizing and vitrifying the glass composition by a crystallization process, wherein the crystallized vitrified glass contains a lithium silicate crystal phase, and the lithium silicate crystal phase has a mass percentage higher than other crystal phases.

[0155] (148) A method for producing crystallized glass according to (146) or (147), wherein the crystallized glass contains, by mass percent, 55 to 80% of SiO2, and / or less than 10% of Al2O3, and / or 8 to 25% of Li2O, and / or 5 to 15% of ZrO2, and / or 1 to 8% of P2O5.

[0156] (149) A method for producing crystallized glass according to any one of (144) to (148), characterized in that the components of the crystallized glass contain, by mass percent, 0 to 5% of a K2O component, and 0 to 5% of a K2O component, and / or 0 to 3% of an MgO component; and / or 0 to 3% of a ZnO component; and / or 0 to 6% of a Na2O component, and / or 0 to 5% of a SrO component, and / or 0 to 5% of a BaO component; and / or 0 to 5% of a CaO component, and / or 0 to 5% of a TiO2 component; and / or 0 to 5% of a B2O3 component; and / or 0 to 6% of a Y2O3 component; and / or 0 to 2% of a fining agent component.

[0157] (150) A method for producing crystallized glass according to any one of (144) to (149), wherein the composition of the crystallized glass satisfies one or more of the following ten conditions in terms of mass percent: 1) Al2O3 / (P2O5+ZrO2) is 1.2 or less, preferably Al2O3 / (P2O5+ZrO2) is 1.0 or less, and more preferably Al2O3 / (P2O5+ZrO2) is 0.05 to 0.7. 2) SiO2 / ZrO2 is 4.0 to 15.8, preferably SiO2 / ZrO2 is 4.5 to 12.0, more preferably SiO2 / ZrO2 is 5.0 to 9.5, and further preferably SiO2 / ZrO2 is 6.0 to 9.0. 3) P2O5+ZrO2 is 6 to 21%, preferably P2O5+ZrO2 is 7 to 18%, more preferably P2O5+ZrO2 is 8 to 16%, and further preferably P2O5+ZrO2 is 10 to 16%. 4) SiO2 / (P2O5+ZrO2) is 2.5 to 12.0, preferably SiO2 / (P2O5+ZrO2) is 3.0 to 10.0, more preferably SiO2 / (P2O5+ZrO2) is 3.5 to 7.5, and further preferably SiO2 / (P2O5+ZrO2) is 4.0 to 6.5. 5) (ZrO2+Li2O) / Al2O3 is 2.0 or more, preferably (ZrO2+Li2O) / Al2O3 is 2.5 or more, and more preferably (ZrO2+Li2O) / Al2O3 is 2.5 to 30.0. 6) (SiO2+Al2O3) / ZrO2 is 4.0 to 16.0, preferably (SiO2+Al2O3) / ZrO2 is 4.5 to 12.0, more preferably (SiO2+Al2O3) / ZrO2 is 5.0 to 10.0, and further preferably (SiO2+Al2O3) / ZrO2 is 6.0 to 9.5. 7) (Li2O+ZrO2) / SiO2 is 0.19 to 0.55, preferably (Li2O+ZrO2) / SiO2 is 0.2 to 0.5, more preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.45, and further preferably (Li2O+ZrO2) / SiO2 is 0.25 to 0.4. 8) (MgO+ZnO) / ZrO2 is 0.65 or less, preferably (MgO+ZnO) / ZrO2 is 0.4 or less, more preferably (MgO+ZnO) / ZrO2 is 0.2 or less, and even more preferably (MgO+ZnO) / ZrO2 is 0.1 or less. 9) (Li2O+Al2O3) / ZrO2 is 0.8 to 5.0, preferably (Li2O+Al2O3) / ZrO2 is 1.0 to 4.0, more preferably (Li2O+Al2O3) / ZrO2 is 1.2 to 3.0, and even more preferably (Li2O+Al2O3) / ZrO2 is 1.5 to 2.5. 10) Li2O / (ZrO2+P2O5) is 0.5 to 3.0, preferably Li2O / (ZrO2+P2O5) is 0.6 to 2.5, more preferably Li2O / (ZrO2+P2O5) is 0.7 to 2.0, and even more preferably Li2O / (ZrO2+P2O5) is 0.8 to 1.5.

[0158] (151) A method for producing crystallized glass according to any one of (144) to (149), wherein the composition of the crystallized glass is, in mass percent, Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.2, even more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.1, and / or Al2O3 / Li2O is 0.4 or less, preferably Al2O3 / Li2O is 0.3 or less, more preferably Al2O3 / Li2O is 0.2 or less, even more preferably Al2O3 / Li2O is 0.1 or less.

[0159] (152) A method for producing crystallized glass according to any one of (144) to (149), wherein the composition of the crystallized glass is, in mass percent, 68 to 78% SiO2 component, preferably 70 to 76% SiO2 component, and / or 0.1 to 4.5% Al2O3 component, preferably 0.5 to 3% Al2O3 component, and / or 12.5 to 22% Li2O component, preferably 12.5 to 20% Li2O component, and / or 6 to 12% ZrO2 component, preferably 7 to 12% ZrO2 component, and / or 1.5 to 7% P2O5 component, preferably 2 to 6% P2O5 component, and / or 0 to 4% K2O component, preferably 0 to 2% K2O component, and / or 0 to 2% MgO component, preferably 0 to 1% MgO component, and and / or 0-2% of a ZnO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0160] (153) A method for producing crystallized glass according to any one of (145) to (149), wherein the composition of the crystallized glass contains, in mass percent, Al2O3 / (Li2O+ZrO2+P2O5) of 0.4 or less, preferably Al2O3 / (Li2O+ZrO2+P2O5) of 0.3 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) of 0.25 or less, and / or Al2O3 / Li2O of 0.7 or less, preferably Al2O3 / Li2O of 0.6 or less, more preferably Al2O3 / Li2O of 0.5 or less, even more preferably Al2O3 / Li2O of 0.45 or less, and / or Al2O3 / (P2O5+ZrO2) of 0.1 to 0.6, and / or (ZrO2+Li2O) / Al2O3 of 3.0 to 20.0.

[0161] (154) A method for producing crystallized glass according to any one of (145) to (149), wherein the composition of the crystallized glass is, in mass percent, 58 to 78% SiO2 component, preferably 60 to 76% SiO2 component, and / or 0.1 to 8% Al2O3 component, preferably 0.5 to 7% Al2O3 component, and / or 9 to 22% Li2O component, preferably 10 to 20% Li2O component, and / or 6 to 12% ZrO2 component, preferably 7 to 12% ZrO2 component, and / or 1.5 to 7% P2O5 component, preferably 2 to 6% P2O5 component, and / or 0 to 4% K2O component, preferably 0 to 2% K2O component, and / or 0 to 2% MgO component, preferably 0 to 1% MgO component, and / or or 0-2% of a ZnO component, preferably 0-1% of a ZnO component, and / or 0-4% of a Na2O component, preferably 0.5-3% of a Na2O component, and / or 0-2% of a SrO component, preferably 0-1% of a SrO component, and / or 0-2% of a BaO component, preferably 0-1% of a BaO component, and / or 0-2% of a CaO component, preferably 0-1% of a CaO component, and / or 0-2% of a TiO2 component, preferably 0-1% of a TiO2 component, and / or 0-3% of a B2O3 component, preferably 0-2% of a B2O3 component, and / or 0-4% of a Y2O3 component, preferably 0-2% of a Y2O3 component, and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

[0162] (155) A method for producing crystallized glass according to any one of (144) to (149), wherein the composition of the crystallized glass contains, in mass percent, 0 to 5% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2, preferably 0 to 2% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2, and more preferably 0 to 1% of La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2.

[0163] (156) A method for producing crystallized glass according to any one of (144) to (149), wherein the composition of the crystallized glass does not contain SrO, and / or BaO, and / or MgO, and / or CaO, and / or ZnO, and / or PbO, and / or As2O3, and / or TiO2, and / or B2O3, and / or Y2O3, and / or F.

[0164] (157) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystal phase contains a lithium silicate crystal phase, and / or a lithium phosphate crystal phase, and / or a petalite crystal phase, and / or a quartz solid solution crystal phase.

[0165] (158) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystal phase contains a lithium silicate crystal phase, and the lithium silicate crystal phase has a mass percentage higher than that of other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is preferably 10 to 70%, more preferably 10 to 65%, further preferably 15 to 60%, and most preferably 20 to 55%.

[0166] (159) A method for producing crystallized glass according to any one of (144) to (149), comprising the step of: providing crystallized glass containing a lithium silicate crystal phase, the lithium silicate crystal phase having a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass being preferably 30 to 65%, more preferably 35 to 60%, and even more preferably 40 to 55%.

[0167] (160) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystal phase contains a lithium disilicate crystal phase, the lithium disilicate crystal phase has a mass percentage higher than that of other crystal phases, and the mass percentage of the lithium disilicate crystal phase in the crystallized glass is preferably 10 to 60%, more preferably 15 to 50%, and even more preferably 20 to 45%.

[0168] (161) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystallized glass contains a lithium phosphate crystal phase, and the mass percentage of the lithium phosphate crystal phase in the crystallized glass is 10% or less, preferably 5% or less.

[0169] (162) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystallized glass contains a quartz solid solution crystal phase, and the mass percentage of the crystallized glass accounted for by the quartz solid solution crystal phase is 10% or less, preferably 5% or less.

[0170] (163) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystallized glass is a crystallized glass containing a petalite crystal phase, and the mass percentage of the petalite crystal phase in the crystallized glass is 18% or less, preferably 15% or less, more preferably 10% or less, and further preferably 5% or less.

[0171] (164) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystallized glass has a crystallinity of 50% or more, preferably 60% or more, more preferably 70% or more, and / or a crystal grain size of 80 nm or less, preferably 50 nm or less, more preferably 30 nm or less, and / or a thermal expansion coefficient of 70×10 -7 / K~90×10 -7 / K; and / or the refractive index is 1.5520 to 1.5700; and / or the body drop height is 1700 mm or more, preferably 1900 mm or more, and more preferably 2000 mm or more; and / or the Vickers hardness is 630 kgf / mm 2 More than 650kgf / mm 2 More preferably, 680kgf / mm 2and / or the relative dielectric constant is 5.4 or more, preferably 5.8 or more, more preferably 6.0 or more; and / or the dielectric loss is 0.05 or less, preferably 0.04 or less, more preferably 0.03 or less, more preferably 0.01 or less; and / or the surface resistance is 1×10 9 Ω cm or more, preferably 1×10 10 Ω cm or more, preferably 1×10 11 Ω·cm or more.

[0172] (165) A method for producing crystallized glass according to any one of (144) to (149), wherein the haze of the crystallized glass having a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less, and / or the average light transmittance at a wavelength of 400 to 800 nm is 87% or more, preferably 89% or more, more preferably 90% or more, and / or the light transmittance at a wavelength of 550 nm is 88% or more, preferably 90% or more, more preferably 91% or more, and / or the average light |B| value at 400 to 800 nm is 0.9 or less, preferably 0.8 or less, more preferably 0.7 or less.

[0173] (166) The method for producing crystallized glass according to (165), wherein the thickness of the crystallized glass is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm or 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0174] (167) A method for producing crystallized glass according to any one of (144) to (149), wherein the crystallized glass contains, as a colorant, by mass percent, 0 to 4% NiO, and / or 0 to 4% Ni2O3, and / or 0 to 2% CoO, and / or 0 to 2% Co2O3, and / or 0 to 7% Fe2O3, and / or 0 to 4% MnO2, and / or 0 to 8% Er2O3, and / or 0 to 8% Nd2O3, and / or 0 to 4% Cu2O, and / or 0 to 8% Pr2O3, and / or 0 to 4% CeO2.

[0175] (168) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.1 to 4% NiO, and / or 0.1 to 4% Ni2O3, and / or 0.05 to 2% CoO, and / or 0.05 to 2% Co2O3, and / or 0.2 to 7% Fe2O3, and / or 0.1 to 4% MnO2, and / or 0.4 to 8% Er2O3, and / or 0.4 to 8% Nd2O3, and / or 0.5 to 4% Cu2O, and / or 0.4 to 8% Pr2O3, and / or 0.5 to 4% CeO2.

[0176] (169) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component, and / or 0.1 to 3% of a Ni2O3 component, and / or 0.05 to 1.8% of a CoO component, and / or 0.05 to 1.8% of a Co2O3 component, and / or 0.2 to 5% of a Fe2O3 component, and / or 0.1 to 3% of a MnO2 component, and / or 0.4 to 6% of a Er2O3 component, and / or 0.4 to 6% of a Nd2O3 component, and / or 0.5 to 3% of a Cu2O component, and / or 0.4 to 6% of a Pr2O3 component, and / or 0.5 to 3% of a CeO2 component.

[0177] (170) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.1 to 3% of a NiO component and / or 0.1 to 3% of a Ni2O3 component.

[0178] (171) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.05 to 1.8% of a CoO component and / or 0.05 to 1.8% of a Co2O3 component.

[0179] (172) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.5 to 3% of a Cu2O component and / or 0.5 to 3% of a CeO2 component.

[0180] (173) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.2 to 5% Fe2O3, 0.05 to 0.3% CoO, or 0.2 to 5% Fe2O3, 0.05 to 0.3% Co2O3, or 0.2 to 5% Fe2O3, 0.05 to 0.3% CoO, 0.1 to 1% NiO, or 0.2 to 5% Fe2O3, 0.05 to 0.3% Co2O3, and 0.1 to 1% NiO.

[0181] (174) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.4 to 6% of a Pr2O3 component, or 0.2 to 5% of an Fe2O3 component, or 0.1 to 3% of an MnO2 component, or 0.4 to 6% of an Er2O3 component, or 0.4 to 6% of an Nd2O3 component.

[0182] (175) A method for producing crystallized glass according to (167), wherein the colorant contains, by mass percent, 0.4 to 6% of an Er2O3 component, 0.4 to 4% of an Nd2O3 component, and 0.1 to 2% of an MnO2 component.

[0183] (176) A method for producing crystallized glass according to any one of (144) to (149), comprising a process of raising the temperature to a predetermined crystallization treatment temperature, holding the temperature for a certain period of time, and then lowering the temperature, wherein the crystallization treatment temperature is 580 to 750°C, preferably 600 to 700°C, and the holding time at the crystallization treatment temperature is 0 to 8 hours, preferably 1 to 6 hours.

[0184] (177) A method for producing crystallized glass according to any one of (144) to (149), comprising carrying out a nucleation process at a first temperature and then carrying out a crystal growth process at a second temperature higher than the temperature of the nucleation process.

[0185] (178) A method for producing crystallized glass according to (177), wherein the crystallization method includes a method in which the first temperature is 470 to 580°C and the second temperature is 600 to 750°C, and the holding time at the first temperature is 0 to 24 hours, preferably 2 to 15 hours, and the holding time at the second temperature is 0 to 10 hours, preferably 0.5 to 6 hours.

[0186] (179) The method for producing a crystallized glass molded body of the present invention comprises grinding or polishing a crystallized glass to produce a crystallized glass molded body, or subjecting a glass composition or a crystallized glass to hot bending or pressing at a certain temperature to produce a crystallized glass molded body.

[0187] (180) A method for producing a crystallized glass molded body, comprising subjecting a glass composition to a primary crystallization heat treatment process including heating, generating nuclei while maintaining the temperature, heating, crystallizing while maintaining the temperature, and cooling to room temperature to form a preliminary crystallized glass, and a crystallized glass molded body can be obtained by hot processing and shaping this preliminary crystallized glass.

[0188] (181) A method for producing a crystallized glass molded body, comprising the following process: 1) Preheating: The glass composition or pre-crystallization glass and crystallized glass are placed in the mold, and the mold is passed through each heating chamber in the hot bending machine in sequence, and kept warm in each chamber for a certain period of time. The temperature in the preheating zone is 400-800°C, the pressure is 0.01-0.05MPa, and the time is 40-200s; 2) Press molding, the mold is preheated and transferred to the molding chamber, and the hot bending machine applies a certain pressure to the mold, the pressure range is 0.1-0.8MPa, the temperature range of the molding chamber is 650-850℃, and the molding time range is 40-200s. 3) Pressure-dwell cooling: The mold is transferred to a cooling chamber and cooled in each chamber, with the temperature drop range of 750 to 500°C, pressure of 0.01 to 0.05 MPa, and time of 40 to 200 s. Effect of the Invention

[0189] The beneficial effect of the present invention is that the crystallized glass or crystallized glass product obtained by the present invention has excellent mechanical properties due to a rational composition design. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0190] The crystallized glass and the crystallized glass product of the present invention are materials having a crystal phase (sometimes called crystal) and a glass phase different from amorphous solids. The crystallized glass and the crystal phase of the crystallized glass can be identified by recognizing the peak angle that appears in the X-ray diffraction pattern of an X-ray diffractometer and / or measuring it by TEMEDX.

[0191] The inventors have determined the content and content ratio of the specific composition that constitutes the crystallized glass and the crystallized glass product to be specific values, and by precipitating a specific crystalline phase, through trial and error, have been able to obtain the crystallized glass or the crystallized glass product of the present invention at a relatively low cost.

[0192] The range of each composition (component) of the glass composition, crystallized glass, and crystallized glass product of the present invention will be described below. In this specification, unless otherwise specified, the content of each composition is expressed as mass percent (wt%) relative to the total amount of the substance of the glass composition, glass crystallized glass, or glass crystallized glass product of the composition converted into oxide. Here, "composition converted into oxide" refers to the total amount of the substance of the oxide being 100% when the oxide, complex salt, hydroxide, etc. used as the raw material of the constituent components of the glass composition, crystallized glass, or crystallized glass product of the present invention decomposes and changes to oxide when melted. In this specification, when simply referring to glass, it refers to the glass composition before crystallization (i.e., crystallization processing), and after the crystallization of the glass composition (i.e., crystallization processing), it is referred to as crystallized glass, and the crystallized glass product refers to the crystallized glass that has been chemically strengthened.

[0193] Numerical ranges described herein include upper and lower limits, and "greater than" and "less than" include the endpoints, and integers and fractions within the range, but are not limited to the specific values ​​set forth when the range is limited. As used herein, the term "about" refers to tolerances, conversion factors, and measurement errors, and may be approximated and / or larger or smaller as necessary, and recipes, parameters, and other quantities and characteristics are not or need not be precise. References to "and / or" herein are inclusive, e.g., "A, and / or B" means A only, B only, or both A and B.

[0194] The crystalline phase of the crystallized glass or crystallized glass product of the present invention comprises a lithium silicate crystalline phase, and / or a lithium phosphate crystalline phase, and / or a petalite crystalline phase, and / or a quartz solid solution crystalline phase.

[0195] In some embodiments of the present invention, the crystalline phase in the crystallized glass or crystallized glass product includes a lithium silicate crystalline phase (one or both of lithium silicate and lithium disilicate). In some embodiments, the lithium silicate crystalline phase has a higher mass percentage than the other crystalline phases. In some embodiments, the lithium silicate crystalline phase is 10-70% of the mass percentage of the crystallized glass or crystallized glass product, preferably the lithium silicate crystalline phase is 10-65% of the mass percentage of the crystallized glass or crystallized glass product, more preferably the lithium silicate crystalline phase is 15-60% of the mass percentage of the crystallized glass or crystallized glass product, and even more preferably the lithium silicate crystalline phase is 20-55% of the mass percentage of the crystallized glass or crystallized glass product. In some embodiments, the lithium silicate crystalline phase is present in an amount of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 109, 104%, 105%, 108, 109, 109, 105, 106, 107, 108, 109, 109, 109, 109, 109, 109, 109 4%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%.

[0196] In some embodiments of the present invention, the crystalline phase in the crystallized glass or crystallized glass product includes a lithium silicate crystalline phase. In some embodiments, the lithium silicate crystalline phase has a higher mass percentage than other crystalline phases. In some embodiments, the lithium silicate crystalline phase is 30-65% by mass in the crystallized glass or crystallized glass product, preferably 35-60% by mass in the crystallized glass or crystallized glass product, and more preferably 40-55% by mass in the crystallized glass or crystallized glass product. In some embodiments, the lithium silicate crystalline phase comprises 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, or 65% by weight of the crystallized glass or crystallized glass article.

[0197] In some embodiments of the present invention, the crystalline phase in the crystallized glass or crystallized glass product comprises a lithium disilicate crystalline phase. In some embodiments, the lithium disilicate crystalline phase has a higher mass percentage than other crystalline phases. In some embodiments, the mass percentage of the lithium disilicate crystalline phase in the crystallized glass or crystallized glass product is 10-60%, preferably the mass percentage of the lithium disilicate crystalline phase in the crystallized glass or crystallized glass product is 15-50%, and more preferably the mass percentage of the lithium disilicate crystalline phase in the crystallized glass or crystallized glass product is 20-45%. In some embodiments, the lithium disilicate crystalline phase comprises 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, or 60% by weight of the crystallized glass or crystallized glass article.

[0198] In some embodiments of the present invention, the crystal phase in the crystallized glass or crystallized glass product includes a lithium phosphate crystal phase, and the lithium phosphate crystal phase is preferably 10% or less by mass in the crystallized glass or crystallized glass product, and the lithium phosphate crystal phase is 5% or less by mass in the crystallized glass or crystallized glass product. In some embodiments, the lithium phosphate crystal phase is 0%, greater than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% by mass in the crystallized glass or crystallized glass product.

[0199] In some embodiments of the present invention, the crystalline phase in the crystallized glass or crystallized glass product includes a quartz solid solution crystalline phase, and the quartz solid solution crystalline phase is preferably 10% or less by mass in the crystallized glass or crystallized glass product, and the quartz solid solution crystalline phase is preferably 5% or less by mass in the crystallized glass or crystallized glass product. In some embodiments, the quartz solid solution crystalline phase is 0%, greater than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% by mass in the crystallized glass or crystallized glass product.

[0200] In some embodiments of the present invention, the crystal phase in the crystallized glass or the crystallized glass product includes a petalite crystal phase. The mass percentage of the petalite crystal phase in the crystallized glass or the crystallized glass product is 18% or less, the mass percentage of the petalite crystal phase in the crystallized glass or the crystallized glass product is preferably 15% or less, the mass percentage of the petalite crystal phase in the crystallized glass or the crystallized glass product is more preferably 10% or less, and the mass percentage of the petalite crystal phase in the crystallized glass or the crystallized glass product is even more preferably 5% or less. In some embodiments, the weight percent of the petalite crystalline phase in the crystallized glass or crystallized glass product is 0%, greater than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, or 18%.

[0201] SiO2 is an essential component of the network structure constituting the glass of the present invention, and is one of the main components that form crystals after heat treatment. If the SiO2 content is 55% or less, the transparency of the glass-crystallized glass and the crystallized glass product formed after the glass crystallization process is not high, and the formation of crystals in the glass-crystallized glass is reduced, which affects the bulk drop height of the glass-crystallized glass and the drop resistance of the crystallized glass product. For this reason, the lower limit of the SiO2 content is 55%, preferably 58%, and more preferably 60%. In some embodiments, the lower limit of the SiO2 content is preferably 65%, more preferably 68%, and even more preferably 70%. On the other hand, if the SiO2 content is 80% or more, glass molding is difficult, glass is difficult to form, the number of types of crystals formed in the crystallized glass changes, and the softening temperature (T s ) increases, which affects the thermal bending of glass and crystallized glass, and further affects the surface stress and the depth of the ion-exchange layer of the crystallized glass product. For this reason, the upper limit of the SiO2 content is 80%, preferably 78%, and more preferably 76%. In some embodiments, the upper limit of the SiO2 content is about 55%, 55.5%, 56%, 56.5%, 57%, 57.5%, 58%, 58.5%, 59%, 59.5%, 60%, 60.5%, 61%, 61.5%, 62%, 62.5%, 63%, 63.5%, 64%, 64.5%, 65%, 65.5%, 66%, 66.5%, 67%, 67.5%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 109%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 126%, 127%, 128%, %, 68%, 68.5%, 69%, 69.5%, 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%, 78.5%, 79%, 79.5%, or 80% SiO2.

[0202] Al2O3 can form a glass network structure, which is advantageous for forming glass, and is also advantageous for chemical strengthening of crystallized glass, improving the drop resistance and bending strength of crystallized glass products. If the content of Al2O3 is too high, other crystals are likely to be generated in the crystallized glass or crystallized glass, and the haze of the crystallized glass or crystallized glass increases. Therefore, the content of Al2O3 in the present invention is less than 10%, preferably 0.1-8%, and more preferably 0.5-7%. In some embodiments, the content of Al2O3 is preferably less than 5%, more preferably 0.1-4.5%, and even more preferably 0.5-3%. In some embodiments, about 0%, greater than 0%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1% ,2.2%,2.3%,2.4%,2.5%,2.6%,2.7%,2.8%,2.9%,3%,3.1%,3.2%,3.3%,3.4%,3.5%,3.6%,3.7%,3.8%,3.9%,4%,4.1%,4.2%,4.3%,4.4%,4.5%,4.6%,4.7%,4.8%, %, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5% , 7.6%, 7.7%, 7.8%, 7.9%, 8%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.7%, 8.8%, 8.9%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, and 10% Al2O3.

[0203] Li2O promotes the melting of glass, lowers the melting temperature of glass, reduces the phase separation of P2O5, promotes the dissolution of P2O5, and forms the main composition of crystals in crystallized glass and crystallized glass products. It is a component that mainly replaces sodium and potassium ions in chemical strengthening, and can increase the surface stress of crystallized glass products, increase the drop ball impact test height of crystallized glass products, and increase the dielectric constant of crystallized glass and crystallized glass products. However, when the content of Li2O is less than 8%, the formation of lithium silicate crystal phase is unfavorable, which affects the depth of the ion exchange layer of crystallized glass, the drop ball impact test height and fragments of crystallized glass and crystallized glass. Therefore, the lower limit of the Li2O content is 8%, preferably 9%, and more preferably 10%. In some embodiments, the lower limit of the Li2O content is more preferably 12.5%. On the other hand, if Li2O is contained in excess, the glass is easily phase separated during the crystallization process, which affects the light transmittance of crystallized glass and crystallized glass. Thus, the upper limit of the Li2O content is 25%, preferably 22%, and more preferably 20%. In some embodiments, about 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, or 25% Li2O may be included.

[0204] Through many experimental studies by the inventors, it has been found that in some embodiments of the present invention, the crystallinity of the crystallized glass and the crystallized glass can be improved and the crystal grain size of the crystallized glass and the crystallized glass can be reduced by controlling the ratio of Al2O3 content to Li2O content, Al2O3 / Li2O, to 0.7 or less. Therefore, it is preferable that Al2O3 / Li2O is 0.7 or less, and it is more preferable that Al2O3 / Li2O is 0.6 or less. Furthermore, in some embodiments, it is also possible to optimize the light transmittance of the crystallized glass and the crystallized glass product and reduce the haze of the crystallized glass and the crystallized glass product by controlling Al2O3 / Li2O to 0.5 or less. Therefore, it is more preferable that Al2O3 / Li2O is 0.5 or less, and it is most preferable that Al2O3 / Li2O is 0.45 or less. In some embodiments, it is preferred that Al2O3 / Li2O is 0.4 or less, more preferred that Al2O3 / Li2O is 0.3 or less, even more preferred that Al2O3 / Li2O is 0.2 or less, and most preferred that Al2O3 / Li2O is 0.1 or less. In some embodiments, the value of Al2O3 / Li2O is 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, It may be 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.55, 0.6, 0.65, 0.7.

[0205] Na2O can lower the melting temperature of glass, effectively lower the exchange rate between Li and Na when chemically strengthening the crystallized glass, and facilitate the control of the chemical strengthening process, and the lower limit of the Na2O content is preferably 0.5%. On the other hand, excessive Na2O content affects the crystal formation in the crystallized glass, reduces the crystallinity of the crystallized glass and the crystallized glass product, and reduces the strength of the crystallized glass and the crystallized glass product. For this reason, the content of Na2O is 0 to 6%, preferably 0 to 4%, and more preferably 0.5 to 3%. In some embodiments, Na2O may be contained in an amount of about 0%, greater than 0%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, or 6%.

[0206] K2O can reduce the viscosity of glass and promote the formation of crystals during the crystallization process, but if it contains too much K2O, the crystals of the crystallized glass or the crystallized glass tend to become coarse, and the light transmittance and the drop ball impact test height of the crystallized glass or the crystallized glass decrease. Therefore, the upper limit of the K2O content is 5%, preferably 4%, and more preferably 2%. In some embodiments, about 0%, greater than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% K2O may be included.

[0207] The P2O5 of the present invention can promote the formation of crystals, improve the crystallinity, increase the hardness and strength, and reduce the haze, and the lower limit of the P2O5 content is 1%, preferably 1.5%, and more preferably 2%. On the other hand, if P2O5 is contained in excess, the crystal distribution becomes non-uniform during glass molding, making it difficult to control the haze and strength of the crystallized glass after heat treatment, and the chemical stability of the glass decreases. Therefore, the upper limit of the P2O5 content is 8%, preferably 7%, and more preferably 6%. In some embodiments, about 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, and 8% P2O5 may be contained.

[0208] In the present invention, by combining ZrO2 and P2O5, the crystal grains can be made fine, and the haze of the crystallized glass and the crystallized glass can be reduced. ZrO2 can increase the network structure of the glass, facilitate the chemical strengthening of the crystallized glass, increase the ion exchange layer depth of the crystallized glass, and improve the height of the falling ball impact test of the crystallized glass. Therefore, the lower limit of the ZrO2 content is 5%, preferably 6%, and more preferably 7%. On the other hand, if ZrO2 is contained in excess, the glass becomes difficult to melt. Therefore, the upper limit of the ZrO2 content is 15%, preferably 12%. In some embodiments, about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or 15% ZrO2 may be included.

[0209] In some embodiments, the haze and |B| value of the glass crystallized glass after heat treatment (for example, heat bending) can be further optimized by controlling the content ratio SiO2 / ZrO2 of SiO2 and ZrO2 within the range of 4.0 to 15.8, and the haze and |B| value of the glass crystallized glass and the crystallized glass product after heat treatment (for example, heat bending) can be made better. Therefore, the range of SiO2 / ZrO2 is preferably 4.0 to 15.8, and the range of SiO2 / ZrO2 is more preferably 4.5 to 12.0. Furthermore, in some embodiments, by setting SiO2 / ZrO2 in the range of 5.0 to 9.5, the ion exchange layer depth of the crystallized glass product can be increased and the drop resistance of the crystallized glass product can be improved, so SiO2 / ZrO2 is more preferably 5.0 to 9.5, and SiO2 / ZrO2 is most preferably 6.0 to 9.0. In some embodiments, the value of SiO2 / ZrO2 can be 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 15.8.

[0210] In some embodiments, the total content of P2O5 and ZrO2, P2O5+ZrO2, is in the range of 6-21%, and the haze of the crystallized glass (including the crystallized glass after heat bending) and the crystallized glass product can be reduced. For this reason, P2O5+ZrO2 is preferably 6-21%, and more preferably 7-18%. Furthermore, in some embodiments, the fracture toughness of the crystallized glass product can be improved by making P2O5+ZrO2 in the range of 8-16%. For this reason, it is more preferable that P2O5+ZrO2 is 8-16%, and most preferably that P2O5+ZrO2 is 10-16%. In some embodiments, the value of P2O5 + ZrO2 can be 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, or 21%.

[0211] In some embodiments, the ratio Al2O3 / (P2O5+ZrO2) of Al2O3 to the total content P2O5 and ZrO2 P2O5+ZrO2 is controlled to 1.2 or less, thereby increasing the crystalline phase content of lithium disilicate in the crystallized glass, and increasing the bulk drop height of the crystallized glass and the drop test height of the crystallized glass product. For this reason, Al2O3 / (P2O5+ZrO2) is preferably 1.2 or less, more preferably 1.0 or less, and even more preferably 0.05 to 0.7. Furthermore, in some embodiments, the haze of the crystallized glass and the crystallized glass product can also be reduced by setting Al2O3 / (P2O5+ZrO2) in the range of 0.1 to 0.6, and therefore, it is most preferable that Al2O3 / (P2O5+ZrO2) is 0.1 to 0.6. In some embodiments, the value of Al2O3 / (P2O5+ZrO2) can be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2.

[0212] In some embodiments, the ratio SiO2 / (P2O5+ZrO2) of the content of SiO2 and the total content P2O5 and ZrO2 P2O5+ZrO2 is controlled to be in the range of 2.5-12.0, which promotes the formation of lithium silicate crystal phase in the crystallized glass, increases the content, inhibits the formation of other crystal phases, effectively guarantees the thermal bending property of the crystallized glass during heat treatment, and improves the thermal bending property of the crystallized glass. For this reason, the range of SiO2 / (P2O5+ZrO2) is preferably 2.5-12.0, and SiO2 / (P2O5+ZrO2) is more preferably 3.0-10.0. Furthermore, in some embodiments, the crystallization of the crystallized glass and the crystallized glass product can be improved by setting SiO2 / (P2O5+ZrO2) to be in the range of 3.5-7.5, and the number of pieces after the breakage of the crystallized glass product can be increased. For this reason, it is more preferred that SiO2 / (P2O5+ZrO2) is 3.5 to 7.5, and most preferred that SiO2 / (P2O5+ZrO2) is 4.0 to 6.5. In some embodiments, the value of SiO2 / (P2O5+ZrO2) can be 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, or 12.0.

[0213] In some embodiments, the ratio (ZrO2+Li2O) / Al2O3 of the total content of Li2O and ZrO2 (ZrO2+Li2O) to the content of Al2O3 is set to 2.0 or more, which can increase the dielectric constant of the crystallized glass and the crystallized glass product, and facilitate subsequent application. Therefore, it is preferable that the range of (ZrO2+Li2O) / Al2O3 is 2.0 or more, more preferably that (ZrO2+Li2O) / Al2O3 is 2.5 or more, and even more preferably that (ZrO2+Li2O) / Al2O3 is 2.5 to 30.0. Furthermore, in some embodiments, the dielectric loss of the crystallized glass and the crystallized glass product can be reduced by setting (ZrO2+Li2O) / Al2O3 in the range of 3.0 to 20.0. Therefore, it is most preferable that (ZrO2+Li2O) / Al2O3 is 3.0 to 20.0. In some embodiments, the value of (ZrO2+Li2O) / Al2O3 is 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23. It may be 0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0, 56.0, 57.0, 58.0, 59.0, or 60.0.

[0214] In some embodiments of the present invention, the ratio (SiO2+Al2O3) / ZrO2 of the total content of SiO2 and Al2O3, SiO2+Al2O3, to the content of ZrO2 is set within the range of 4.0-16.0, so that the glass crystallized glass and the crystallized glass product can be given an appropriate surface resistance, and subsequent use can be facilitated. For this reason, (SiO2+Al2O3) / ZrO2 is preferably 4.0-16.0, and (SiO2+Al2O3) / ZrO2 is more preferably 4.5-12.0. Furthermore, in some embodiments, by controlling (SiO2+Al2O3) / ZrO2 within the range of 5.0-10.0, the change in the content of the crystalline phase after further heat treatment (e.g., heat bending) of the crystallized glass can be reduced, and the dimensions of the crystallized glass after heat treatment (e.g., heat bending) can be easily controlled, and subsequent processing can be facilitated. Therefore, it is more preferable that (SiO2+Al2O3) / ZrO2 is 5.0 to 10.0, and most preferable that (SiO2+Al2O3) / ZrO2 is 6.0 to 9.5. In some embodiments, the value of (SiO2+Al2O3) / ZrO2 may be 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, or 16.0.

[0215] Through extensive experimental research by the inventors, it has been found that there exists a complex synergy between Al2O3, Li2O, ZrO2 and P2O5. In some embodiments of the present invention, by controlling Al2O3 / (Li2O+ZrO2+P2O5) to 0.4 or less, the height of the falling ball impact test of the crystallized glass and the crystallized glass product can be improved, so that Al2O3 / (Li2O+ZrO2+P2O5) is preferably 0.4 or less, more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.3 or less, and even more preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.25 or less. In some embodiments, by controlling Al2O3 / (Li2O+ZrO2+P2O5) to the range of 0.01-0.2, the haze and light transmittance of the crystallized glass and the crystallized glass product can also be optimized. For this reason, Al2O3 / (Li2O+ZrO2+P2O5) is most preferably 0.01 to 0.2, and further most preferably Al2O3 / (Li2O+ZrO2+P2O5) is 0.01 to 0.1. In some embodiments, the value of Al2O3 / (Li2O+ZrO2+P2O5) can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, or 0.4.

[0216] In some embodiments of the present invention, the ratio (Li2O+ZrO2) / SiO2 of the total content of Li2O and ZrO2 (Li2O+ZrO2) to the content of SiO2 is set to a range of 0.19 to 0.55, thereby improving the hardness and ball drop impact test height of the crystallized glass and the crystallized glass product. For this reason, it is preferable that (Li2O+ZrO2) / SiO2 is 0.19 to 0.55, and it is more preferable that (Li2O+ZrO2) / SiO2 is 0.2 to 0.5. Furthermore, in some embodiments, the |B| value of the crystallized glass and the crystallized glass product can be reduced by setting (Li2O+ZrO2) / SiO2 within a range of 0.25 to 0.45. For this reason, it is more preferred that (Li2O+ZrO2) / SiO2 be between 0.25 and 0.45, and most preferred that (Li2O+ZrO2) / SiO2 be between 0.25 and 0.4. In some embodiments, the value of (Li2O+ZrO2) / SiO2 is 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0. 26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.51, 0.52, 0.53, 0.54, 0.55.

[0217] In some embodiments of the present invention, the bending strength of the glass-ceramic glass and the crystallized glass product can be improved by controlling the ratio (Li2O+Al2O3) / ZrO2 of the total content Li2O and Al2O3 Li2O+Al2O3 to the ZrO2 content in the range of 0.8 to 5.0. Therefore, it is preferable that (Li2O+Al2O3) / ZrO2 is 0.8 to 5.0, and it is more preferable that (Li2O+Al2O3) / ZrO2 is 1.0 to 4.0. Furthermore, it is possible to further optimize the chemical durability of the crystallized glass by controlling (Li2O+Al2O3) / ZrO2 to 1.2 to 3.0, and it is possible to improve the ion exchange layer depth and surface stress of the crystallized glass. Therefore, it is more preferable that (Li2O+Al2O3) / ZrO2 is 1.2 to 3.0, and it is most preferable that (Li2O+Al2O3) / ZrO2 is 1.5 to 2.5. In some embodiments, the value of (Li2O+Al2O3) / ZrO2 can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.

[0218] In some embodiments of the present invention, the ratio Li2O / (ZrO2+P2O5) of the content of Li2O to the total content ZrO2 and P2O5 ZrO2+P2O5 is controlled to a range of 0.5 to 3.0, thereby reducing the |B| value and grain size of the crystallized glass and the crystallized glass product. For this reason, Li2O / (ZrO2+P2O5) is preferably 0.5 to 3.0, and Li2O / (ZrO2+P2O5) is more preferably 0.6 to 2.5. Furthermore, by setting Li2O / (ZrO2+P2O5) to a range of 0.7 to 2.0, the chemical durability of the crystallized glass can be optimized, and the ion exchange layer depth and fracture toughness of the crystallized glass can be improved. For this reason, Li2O / (ZrO2+P2O5) is more preferably 0.7 to 2.0, and Li2O / (ZrO2+P2O5) is most preferably 0.8 to 1.5. In some embodiments, the value of Li2O / (ZrO2+P2O5) is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6 , 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3.0.

[0219] ZnO reduces the difficulty of melting glass, and if the content is too high, it can promote low-temperature phase separation of glass and reduce the crystallinity of glass crystallized glass and crystallized glass products, and the upper limit of the content of ZnO is 3%, preferably 2%, more preferably 1%, and even more preferably does not contain ZnO. In some embodiments, about 0%, more than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3% ZnO may be included.

[0220] MgO is advantageous in reducing the melting difficulty of glass and increasing the height of crystallized glass or crystallized glass in the falling ball impact test, but it promotes the low-temperature crystallization of glass and tends to reduce the crystallinity and light transmittance of crystallized glass or crystallized glass. Therefore, the upper limit of the content of MgO is 3%, preferably 2%, more preferably 1%, and even more preferably no MgO is contained. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% MgO may be included.

[0221] In some embodiments of the present invention, the ratio (MgO+ZnO) / ZrO2 of the total content of MgO and ZnO to the content of ZrO_2 is controlled to 0.65 or less, thereby improving the hardness, bending strength and fracture toughness of the glass-ceramic glass and the crystallized glass product. Therefore, (MgO+ZnO) / ZrO2 is preferably 0.65 or less, more preferably 0.4 or less, even more preferably 0.2 or less, and most preferably 0.1 or less. In some embodiments, the value of (MgO+ZnO) / ZrO2 can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65.

[0222] SrO is an optional component for improving the low-temperature melting property of glass and suppressing crystallization during glass molding, but if the content is too high, it is disadvantageous for glass molding. Therefore, the content of SrO in the present invention is 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and further preferably no SrO is contained. In some embodiments, it can contain about 0%, more than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% SrO.

[0223] BaO is an optional component that helps improve the glass formability of glass, and if the content is too high, it is disadvantageous to the forming of glass. Therefore, the content of BaO in the present invention is 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and even more preferably no BaO is contained. In some embodiments, it can contain about 0%, more than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% BaO.

[0224] CaO can increase the hardness of glass, and if the content is too high, the glass is easily emulsified during molding. Therefore, the CaO content in the present invention is in the range of 0 to 5%, preferably 0 to 2%, more preferably 0 to 1%, and more preferably no CaO is contained. In some embodiments, the glass may contain about 0%, more than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% CaO.

[0225] TiO2 is an optional component that contributes to lowering the melting temperature of glass and improving chemical stability, and in the present invention, by containing 5% or less of TiO2, it is possible to easily control the crystallization process of glass, and preferably contains 2% or less, more preferably contains 1% or less of TiO2. In some embodiments, it is even more preferable to not contain TiO2. In some embodiments, about 0%, more than 0%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% TiO2 may be contained.

[0226] B2O3 can improve the network structure of glass and adjust the chemical durability of crystallized glass, and if its content exceeds 5%, it is disadvantageous for glass forming and is prone to crystallization during forming, so the upper limit of the B2O3 content is set to 5%, preferably 3%, more preferably 2%, and even more preferably no B2O3 is contained. In some embodiments, it can contain about 0%, greater than 0%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% B2O3.

[0227] Y2O3 promotes the dissolution of ZrO2 and reduces the difficulty of dissolving glass. If the content is too high, it becomes difficult to form crystals during glass crystallization, the crystallinity of the crystallized glass and the crystallized glass product decreases, and the height of the crystallized glass and the crystallized glass product in the falling ball impact test decreases. Therefore, the upper limit of the content of Y2O3 is 6%, preferably 4%, and more preferably 2%. In some embodiments, it can contain about 0%, more than 0%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% Y2O3.

[0228] In some embodiments, the glass, crystallized glass or crystallized glass product may further contain 0-2% of a fining agent to improve the degassing ability of the glass, crystallized glass or crystallized glass product, the fining agent including, but not limited to, one or more of Sb2O3, SnO2, SnO, CeO2, F (fluorine), Cl (chlorine) and Br (bromine), preferably Sb2O3. When the fining agent is present alone or in combination, the upper limit of its content is preferably 1%, more preferably 0.5%. In some embodiments, the content of one or more of the fining agents is about 0%, greater than 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%.

[0229] The performance of the glass, crystallized glass or crystallized glass product of the present invention can be improved without affecting the performance of the glass, crystallized glass or crystallized glass product.Other components not listed above, such as La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, TeO2, GeO2, etc. can be added as appropriate, but in order to maintain the excellent properties of the glass, crystallized glass or crystallized glass of the application, the content or total content of La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, TeO2, GeO2 is 5% or less, preferably 2% or less, more preferably 1% or less, and even more preferably none.

[0230] Since PbO and As2O3 are harmful substances and do not meet the requirements for environmental protection even in small amounts, in some embodiments, it is preferred that the present invention does not include PbO and As2O3.

[0231] In some embodiments of the present invention, a glass composition, crystallized glass, or crystallized glass product having color can be produced by containing a colorant, and the glass composition, crystallized glass, or crystallized glass product can exhibit different colors, and the colorant is 0-4% NiO component, and / or 0-4% Ni2O3 component, and / or 0-2% CoO component, and / or 0-2% Co2O3 component, and / or 0-7% Fe2O3 component, and / or 0-4% MnO2 component, and / or 0-8% Er2O3 component, and / or 0-8% Nd2O3 component, and / or 0-4% Cu2O component, and / or 0-8% Pr2O5 component, and / or 0-4% CeO2 component. The mass percent content of the colorant and its action are described in detail as follows.

[0232] The brown or green glass composition, crystallized glass or crystallized glass product produced by the present invention uses NiO, Ni2O3 or Pr2O5 as a colorant. NiO and Ni2O3 are colorants. The two components used to prepare the brown or green glass composition, crystallized glass or crystallized glass product have a respective content of generally 4% or less, preferably 3% or less. If the content exceeds 4%, the colorant does not dissolve well in the glass composition, crystallized glass or crystallized glass product. The lower limit of each content is 0.1% or more, and if it is less than 0.1%, the color of the glass composition, crystallized glass or crystallized glass product is not noticeable. They can be used alone or mixed. In some embodiments, it may contain about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% NiO or Ni2O3. When used in combination, the total amount of NiO and Ni2O3 is generally 4% or less, and the lower limit of the total amount is generally 0.1% or more. In some embodiments, the NiO and Ni2O3 may include about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%. Pr2O5 is used alone as a colorant for a green glass composition, crystallized glass, or crystallized glass product. The general content is 8% or less, preferably 6% or less. If the lower limit of the content is 0.4% or more and less than 0.4%, the color of the glass composition, crystallized glass, or crystallized glass product is not noticeable.In some embodiments, Pr2O5 may be present at about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, or 8.0%.

[0233] The blue glass composition, crystallized glass or crystallized glass product produced by the present invention uses CoO or Co2O3 as a colorant. The two colorant components can be used alone or in mixture, and the respective contents are generally 2% or less, preferably 1.8% or less. If the content exceeds 2%, the colorant does not dissolve well in the glass composition, crystallized glass or crystallized glass product. The lower limit of each content is 0.05% or more, and if it is less than 0.05%, the color of the glass composition, crystallized glass or crystallized glass product is not noticeable. In some embodiments, it can contain about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% CoO or Co2O3. When used in combination, the total amount of CoO and Co2O3 does not exceed 2%, with a lower limit of the total amount being 0.05% or more. In some embodiments, the composition may contain about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% CoO and Co2O3.

[0234] The yellow glass composition, crystallized glass or crystallized glass product produced by the present invention uses Cu2O or CeO2 as a colorant, and the two types of colorant components are used alone or in combination, and if the lower limit of each content is 0.5% or more and less than 0.5%, the color of the glass composition, crystallized glass or crystallized glass product is not noticeable. When Cu2O alone is 4% or less, preferably 3% or less, and the content exceeds 4%, the glass composition is easily crystallized. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% Cu2O may be included. The content of CeO2 is generally 4% or less, preferably 3% or less, and if it exceeds 4%, the luster of the glass composition, the crystallized glass or the crystallized glass product will be deteriorated. In some embodiments, CeO2 may be present at about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, or 4.0%. On the other hand, when a small amount of CeO2 is added to glass, it has a bubble removing effect, and CeO2 can also be used as a clarifier. When used as a clarifier, its content is 2% or less, preferably 1% or less, and more preferably 0.5% or less. When two types of colorants are mixed and used, their total content is generally 4% or less, and the lower limit of the total content is 0.5% or more.In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% CeO2 and Cu2O may be included.

[0235] A black or smoke gray glass composition, crystallized glass or crystallized glass product manufactured using Fe2O3 alone as a colorant, or a colorant using a mixture of two types of Fe2O3 and CoO is used. Or a colorant using a mixture of two types of Fe2O3 and Co2O3 is used. Or a colorant using a mixture of three types of Fe2O3, CoO and NiO is used. Or a colorant using a mixture of three types of Fe2O3, Co2O3 and NiO is used. The colorant for preparing the black and smoke gray glass composition, crystallized glass or crystallized glass product is mainly colored using Fe2O3, and its content is 7% or less, preferably 5% or less, and the lower limit of its content is 0.2% or more, and in some embodiments, it is about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%. , 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0% Fe2O3. CoO and Co2O3 are absorbed in visible light and can deepen the coloring of glass compositions, crystallized glass or crystallized glass products. Generally, when mixed with Fe2O3, the respective contents are not more than 0.6%, and the lower limit is not less than 0.2%. In some embodiments, it may contain about 0.2%, 0.3%, 0.4%, 0.5%, 0.6% CoO and / or Co2O3. NiO absorbs visible light and can deepen the coloring degree of the glass composition, crystallized glass or crystallized glass product, and when used in a mixture, its content is generally 1% or less, and the lower limit of the total amount is 0.2% or more. In some embodiments, it may contain about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0% NiO.

[0236] The purple glass composition, crystallized glass or crystallized glass product produced by the present invention uses MnO2 as a colorant, and its content is generally 4% or less, preferably 3% or less. If the lower limit of the content is 0.1% or more and less than 0.1%, the color of the glass composition, crystallized glass or crystallized glass product is not noticeable. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% MnO2 may be included.

[0237] The pink glass composition, crystallized glass or crystallized glass product produced by the present invention uses Er2O3 as a colorant, and the content is generally 8% or less, preferably 6% or less. Because the coloring efficiency of the rare earth element Er2O3 is low, even if the content exceeds 8%, the color of the glass composition, crystallized glass or crystallized glass product cannot be deepened, but rather increases the cost. The lower limit of the content is 0.4% or more, and if it is less than 0.4%, the color of the glass composition, crystallized glass or crystallized glass product is not clear. In some embodiments, Er2O3 may be present at about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, or 8.0%.

[0238] The purple-red glass composition, crystallized glass or crystallized glass product produced by the present invention uses Nd2O3 as a colorant, generally in an amount of 8% or less, preferably 6% or less. Because the coloring efficiency of rare earth element Nd2O3 is low, even if the amount exceeds 8%, the color of the glass composition, crystallized glass or crystallized glass product cannot be deepened, but the cost increases. The lower limit of the content is 0.4% or more. If it is less than 0.4%, the color of the glass composition, crystallized glass or crystallized glass product is not clear. In some embodiments, about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, or 8.0% Nd2O3 may be included.

[0239] The red glass composition, crystallized glass or crystallized glass product prepared by the present invention uses Er2O3, Nd2O3 and MnO2 to mix colorants. The Er ions in the glass are absorbed at 400-500nm, Mn ions are mainly absorbed at 500nm, and Nd ions are mainly strongly absorbed at 580nm. By mixing the three substances, the red glass composition, crystallized glass or crystallized glass product can be prepared. Er2O3 and Nd2O3 are rare earth colorants, so their coloring ability is relatively weak, and the amount of Er2O3 used is within 6%, the amount of Nd2O3 used is within 4%, and the coloring of MnO2 is strong, and the amount used is within 2%, and the lower limit of the total amount of mixed colorants used is above 0.9%.

[0240] The phrase "does not contain 0%" as used herein means that the compound, molecule, element, etc. is not intentionally added as a raw material to the glass composition, crystallized glass, or crystallized glass product of the present invention. However, impurities or components that are not intentionally added may exist as raw materials and / or equipment for producing the glass composition, crystallized glass, or crystallized glass product, and may be contained in small or trace amounts in the final glass composition, crystallized glass, or crystallized glass product, and such cases are also within the scope of protection of the present invention patent.

[0241] In some embodiments of the present invention, the crystallized glass and the crystallized glass product of the present invention contain lithium silicate in the crystal phase, which provides high strength and high fracture toughness to the crystallized glass and the crystallized glass product of the present invention, and the crystallized glass and the crystallized glass product have high drop ball impact test height and four-point bending strength. The crystallized glass of the present invention has excellent chemical durability and can be treated by chemical strengthening to obtain excellent mechanical strength. By rational composition design, the crystallized glass and the crystallized glass product of the present invention can obtain an appropriate crystal grain size and have high strength. According to the present invention, it is possible to provide a crystallized glass and a crystallized glass product having excellent mechanical properties due to good crystallinity. The crystallinity referred to in this text refers to the degree of completion of the crystal, and the arrangement of the mass points inside the crystal of a completed crystal is relatively regular, the diffraction lines are strong, sharp and symmetrical, and the half-width of the diffraction peak is close to the width measured by the instrument, and the crystal with poor crystallinity has defects such as dislocations, and the peak shape of the diffraction lines is widely dispersed. The worse the crystallinity, the weaker the diffraction ability, and the diffraction peak becomes wider until it disappears into the background. In some embodiments, the crystallinity of the crystallized glass article or glass is 50% or more, preferably 60% or more, and more preferably 70% or more.

[0242] The size and type of crystal grains in the crystallized glass or crystallized glass of the present invention affect the haze and transmittance of the crystallized glass or crystallized glass, the smaller the crystal grains, the higher the transmittance, and the smaller the haze, the higher the transmittance.In some embodiments, the haze of the crystallized glass product or crystallized glass with a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less.In some embodiments, the crystal grain size of the crystallized glass product or crystallized glass is 80 nm or less, preferably 50 nm or less, more preferably 30 nm or less.

[0243] In some embodiments, the present invention provides a crystallized glass or a crystallized glass product, characterized in that the crystal phase content and refractive index in the crystallized glass or the crystallized glass product affect the |B| value of the crystallized glass or the crystallized glass product, and when the crystallized glass or the crystallized glass product is observed in the visible light region, it becomes blue or yellowish, affecting the optical performance of the product, and is labeled with the |B| value in LAB (colorimetry of material color). The crystallized glass or the crystallized glass shows a low |B| value in the visible light region, and in some embodiments, the average light |B| value at 400 to 800 nm of the crystallized glass or the crystallized glass with a thickness of 1 mm or less is 0.9 or less, preferably 0.8 or less, more preferably 0.7 or less.

[0244] In some embodiments, the crystallized glass or crystallized glass product of the present invention exhibits high transparency in the visible light region (i.e., the crystallized glass or crystallized glass product is transparent). The crystallized glass or crystallized glass exhibits high transmittance in the visible light region, and in some embodiments, the average light transmittance of the crystallized glass or crystallized glass having a thickness of 1 mm or less at 400 to 800 nm is preferably 87% or more. In some preferred embodiments, the light transmittance of the crystallized glass product or crystallized glass having a thickness of 1 mm or less at 550 nm is preferably 88% or more.

[0245] In some embodiments, antimicrobial components may be added to the glass composition, the crystallized glass, or the crystallized glass product. The crystallized glass or the crystallized glass product described herein may be used in applications such as kitchens or dining tables where there is a high probability of exposure to harmful bacteria. The antimicrobial components included in the glass composition, the crystallized glass, or the crystallized glass product include, but are not limited to, Ag, AgO, Cu, CuO, Cu2O, and the like. In some embodiments, the content of the above antimicrobial components alone or in combination is 2% or less, preferably 1% or less.

[0246] The glass composition, crystallized glass and crystallized glass product of the present invention are produced and can be produced by the following methods. The ingredients for the glass composition are mixed uniformly according to the ratio of ingredients, and the uniform mixture is placed in a platinum or quartz crucible, and melted in an electric or gas furnace at a temperature range of 1250 to 1650°C for 5 to 24 hours depending on the difficulty of melting the glass composition. After melting and stirring to make it uniform, the temperature is lowered to an appropriate level, poured into a mold, and cooled slowly to obtain the glass composition.

[0247] The glass composition of the present invention can be shaped by known methods.

[0248] The glass composition of the present invention is subjected to a crystallization treatment by a crystallization method after molding or processing, so that crystals are uniformly precipitated inside the glass. This crystallization treatment may be performed in one step or two steps, and is preferably performed in two steps. After the treatment by the nucleation method is performed at a first temperature, the treatment by the crystal growth method is performed at a second temperature higher than the temperature of the nucleation method. The crystallization treatment performed at the first temperature is called the first crystallization treatment, and the crystallization treatment performed at the second temperature is called the second crystallization treatment.

[0249] In order to give the crystallized glass the desired physical properties, the preferred crystallization process is as follows. By carrying out the crystallization process in one step as described above, the nucleation process and the crystal growth process can be carried out continuously. That is, the temperature is raised to a predetermined crystallization process temperature, and after reaching the crystallization process temperature, the temperature is maintained for a certain period of time and then lowered. The crystallization process temperature is preferably 580 to 750°C, more preferably 600 to 700°C in order to precipitate the desired crystal phase, and the holding time at the crystallization process temperature is preferably 0 to 8 hours, more preferably 1 to 6 hours.

[0250] When the crystallization treatment is carried out in two stages, the first temperature is preferably 470 to 580° C., and the second temperature is preferably 600 to 750° C. The holding time at the first temperature is preferably 0 to 24 hours, more preferably 2 to 15 hours. The holding time at the second temperature is preferably 0 to 10 hours, more preferably 0.5 to 6 hours.

[0251] The above-mentioned holding time of 0 hours means that the temperature is increased or decreased again in less than one minute after reaching the temperature.

[0252] In some embodiments, the glass compositions or crystallized glasses described herein may be manufactured into bodies by various processes, including, but not limited to, sheets, including, but not limited to, slot drawing, float, roll pressing, and other techniques. Alternatively, the glass compositions or crystallized glasses can be formed by float or roll pressing methods known to those skilled in the art. The bodies of the present invention further include lenses, prisms, and the like.

[0253] The glass composition or crystallized glass of the present invention can be used to manufacture a sheet-shaped glass molded body or a crystallized glass molded body using methods such as grinding and polishing, but the manufacturing method of the glass molded body or the crystallized glass molded body is not limited to these methods.

[0254] The glass composition or crystallized glass of the present invention can be used to manufacture glass molded bodies or crystallized glass molded bodies that are formed into various shapes at a certain temperature using methods such as hot bending and pressing, but are not limited to these methods.

[0255] In some embodiments, glass molded body or crystallized glass molded body can be manufactured by hot bending method.Hot bending method is the method of placing 2D or 2.5D glass or crystallized glass in a mold, and sequentially carrying out the processes of heating up preheating, press molding, and pressure keeping and cooling down in a hot bending machine to manufacture three-dimensional curved glass molded body or crystallized glass.

[0256] In some embodiments, the crystallized glass molding has a 2.5D or 3D structure, i.e., the crystallized glass molding has a non-planar structure.As described herein, "non-planar structure" means that in a 2.5D or 3D shape, at least a portion of the crystallized glass molding extends outward or along an angle with the plane defined by the original layout configuration of the 2D glass composition.The 2.5D or 3D crystallized glass molding formed from the glass composition may have one or more convex or curved portions.

[0257] In some embodiments, the method for producing a crystallized glass molded body is a hot bending method, taking into consideration the characteristics such as the growth of the crystal phase in the crystallized glass and the transition of the crystal phase. Specifically, the method of the present invention includes pre-crystallization and forming by hot working. The pre-crystallization of the present invention is characterized in that the crystallization process of a glass composition (i.e., glass before crystallization) is controlled to form a pre-crystallized glass having a crystallization degree that does not reach the crystallization degree required for the performance index of the intended crystallized glass molded body. This pre-crystallized glass is formed into a crystallized glass molded body through a hot working forming method.

[0258] In some embodiments, the method for producing a crystallized glass body includes the following steps. 1) A primary crystallization heat treatment process including glass composition, heating, heat-retention nucleation, heating, heat-retention crystallization, and cooling to room temperature is carried out to form a pre-crystallized glass. 2) This pre-crystallized glass can be molded by hot working to obtain a crystallized glass molded body.

[0259] The crystallization heat treatment method of the present invention is a method for crystallizing a glass composition by nucleating the glass composition at a certain temperature Th and a certain time th, and then crystallizing the glass composition by nucleating the glass composition at a certain temperature Tc and a certain time t c The crystallization degree of the obtained pre-crystallized glass does not reach the crystallization degree required for the performance index of the intended crystallized glass molding. Using XRD test data, the Rietveld full spectrum fitting method was used to determine the total content of the main crystalline phase in the crystallization degree of the pre-crystallized glass. c1 It was calculated that the pre-crystallization of the present invention is a complete process including a nucleation step, one, two or three or more stages of crystallization, and is a complete process of heating, keeping warm, heating again, keeping warm, etc., and then cooling down to room temperature through the process. Unlike the primary crystallization, secondary crystallization, etc. mentioned in some documents or patents, the present invention is actually only the first stage crystallization, the second stage crystallization, etc. in the complete crystallization process, and the intermediate stages are continuous, and there is no process of cooling down to room temperature and then heating again to crystallize.

[0260] The hot-worked molded product of the present invention is prepared by subjecting pre-crystallized glass to a hot-working forming process including, but not limited to, multiple hot-working processes, such as press forming, bending forming, or drawing, under certain conditions of temperature, time, pressure, etc. In the hot-working forming process, a molded body having a complex shape may not be completed in one hot-working process, and may require multiple hot-working processes of two or more processes.

[0261] In some embodiments, the method for producing a crystallized glass molded body is a hot bending method. Specifically, in some embodiments, the method for producing a crystallized glass molded body includes the following steps. 1) The preheating component is placed in a mold as a glass composition or pre-crystallized glass or glass-crystallized glass, and the mold passes through each heating chamber in sequence in the hot bending machine, staying in each chamber for a certain time to keep warm. The temperature of the preheating chamber is 400-800°C, the pressure is 0.01-0.05MPa, and the time is 40-200s. In some embodiments, for a hot bending machine with five preheating chambers, the initial heating stable setting is generally about 500°C, and the subsequent chambers are gradually heated, and the temperature gradient between the two adjacent chambers gradually decreases from low temperature to high temperature, and the temperature difference between the last preheating chamber and the first chamber of the press mold can be within a range of 20°C. 2) The press-molding components are transferred to the molding chamber after preheating, and the hot bending machine applies a certain pressure to the mold, the pressure range is 0.1-0.8MPa, the pressure magnitude is determined by factors such as glass thickness and radian, the temperature range of the molding chamber is 650-850℃, and the molding time range is 40-200s. 3) The pressure-holding cooling component is transferred to the cooling chamber and the mold is cooled in each chamber. The temperature drop range is 750 to 500°C, the pressure is 0.01 to 0.05 MPa, and the time is 40 to 200 s.

[0262] Crystallized glass moldings need to be shaped by hot bending, and like general high-aluminum glass, their appearance quality needs to be controlled. In addition, like 3D curved glass used for display devices and electronic device housings, the effect of crystal growth during hot bending on the performance of the glass needs to be controlled, and attention needs to be paid to the light transmittance, haze, |B| value, and their uniformity after hot bending.

[0263] In some embodiments, the main crystal phase of the pre-crystallized glass includes lithium silicate, and / or lithium disilicate, and / or lithium phosphate, and / or quartz solid solution, and / or lithium permeable feldspar, and the content of the crystal phase is 20-60%, and the content of the lithium permeable feldspar is 0-18%. The crystallized glass molded body formed after molding by hot bending method includes the main crystal phase of lithium disilicate, or lithium disilicate and lithium permeable feldspar, and the content of the crystal phase is in the range of 40-70%, and the content of the lithium permeable feldspar is 0-18%.

[0264] In some embodiments, the main crystal phase of the pre-crystallized glass includes lithium silicate, and / or lithium disilicate, and / or lithium phosphate, and / or quartz solid solution, and / or lithium permeable feldspar, and the content of the crystal phase is 20-60%, where the content of the lithium permeable feldspar is 0-18%.The crystallized glass molding formed after being molded by hot bending method, the main crystal phase includes lithium silicate and / or lithium disilicate, and the content of the crystal phase is in the range of 40-70%.

[0265] The amount of change in crystalline phase before and after hot bending determines the dimensional uniformity, mass production feasibility, cost control, etc. of the crystallized glass molding, and the crystallized glass molding has excellent hot workability, and the change in crystalline phase content after hot bending is 20% or less, preferably 15% or less, and more preferably 10% or less, and the uniformity of the haze, |B| value, etc. of the crystallized glass molding obtained after hot bending can be ensured.

[0266] The glass compositions, crystallized glasses and crystallized glass products described in this invention can have any reasonably useful thickness.

[0267] The crystallized glass of the present invention has improved mechanical properties due to precipitation crystallization, and further excellent mechanical properties can be obtained by forming a compressive stress layer, making it possible to form a crystallized glass product.

[0268] In some embodiments, the glass composition or crystallized glass may be processed into a sheet and / or shaped (e.g., punched, hot bent, etc.), polished and / or swept after setting, and chemically strengthened by a chemical strengthening process.

[0269] The chemical strengthening method of the present invention is an ion exchange method. In the ion exchange process, smaller metal ions in a glass composition or crystallized glass are replaced or "exchanged" with larger metal ions having the same valence close to that of the glass composition or crystallized glass. By replacing the larger ions with smaller ions, compressive stress is built up in the glass composition or crystallized glass, forming a compressive stress layer.

[0270] In some embodiments, the metal ions are monovalent alkali metal ions (e.g., Na+, K+, Rb+, Cs+, etc.), and the ion exchange is performed by immersing the glass composition or glass-ceramic glass in a salt bath containing at least one molten salt of a large metal ion used to replace the small metal ions in the glass composition. Also, other monovalent metal ions, such as Ag + , Tl + , Cu + etc. may also be used for monovalent ion exchange. The one or more ion exchange processes for chemically strengthening the glass compositions or glass-ceramics may include, but are not limited to, immersing them in a single salt bath or immersing them in multiple salt baths having the same or different compositions, with washing and / or annealing processes in between.

[0271] In some embodiments, the glass composition or crystallized glass may be ion-exchanged for about 1 to 36 hours in a salt bath of molten Na salt (e.g., NaNO3) immersed at about 350°C to 470°C, preferably 380°C to 460°C, preferably in the range of 2 to 24 hours. In this embodiment, the Na ions replace some of the Li ions in the glass composition or crystallized glass, thereby forming a surface compression layer and exhibiting high mechanical properties. In some embodiments, the glass composition or crystallized glass may be ion-exchanged by immersing the glass composition or crystallized glass in a molten salt bath of K salt (e.g., KNO3) at a temperature of about 360°C to 450°C for 1 to 36 hours, preferably in the range of 2 to 24 hours. In some embodiments, the glass composition or crystallized glass may be ion-exchanged by immersing the glass composition or crystallized glass in a mixed salt bath of molten K salt and Na salt at a temperature of about 360°C to 450°C, preferably in the range of 2 to 24 hours, for 1 to 36 hours.

[0272] The performance indicators of the crystallized glass and / or crystallized glass product and / or glass composition of the present invention are tested using the following methods.

[0273] [Hayes] Using a Minolta CM3600A haze tester, samples of less than 1 mm were prepared and tested based on GB2410-80.

[0274] [Grain size] Measurements were performed using a SEM scanning electron microscope. After surface treatment in HF acid, gold was sprayed onto the surface of the crystallized glass, and the surface was scanned under a SEM scanning electron microscope to determine the grain size.

[0275] [Light transmittance] All light transmittances mentioned in this paper are external transmittances, and may be abbreviated to transmittance. The sample was processed to a thickness of 1 mm or less, the opposing surfaces were parallel-polished, and the average light transmittance from 400 to 800 nm was measured using a Hitachi U-41000 spectrophotometer. The sample was processed to a thickness of 1 mm or less, the opposing surfaces were polished to be parallel, and the light transmittance at 550 nm was measured using a Hitachi U-41000 spectrophotometer.

[0276] [Crystallina] The degree of crystallinity is calculated by comparing the XRD diffraction peaks with database images and calculating the ratio of the crystalline phase diffraction intensity to the total image intensity, and internal calibration is performed using pure quartz.

[0277] [Ion exchange layer depth] The depth of the ion-exchange layer was measured using a glass surface stress meter SLP-2000. The measurement conditions are calculated as follows: the refractive index of the sample is 1.56, and the photoelastic constant is 26 [(nm / cm) / MPa].

[0278] [Height of the falling ball impact test] A crystallized glass product sample of 145mm x 67mm x 0.7mm is placed on a glass transport jig, and a steel ball of 132g is dropped from a specified height. This is the maximum drop test height that the sample can withstand without breaking. Specifically, the test is performed from a drop ball impact test height of 800mm, and the height is changed sequentially to 850mm, 900mm, 950mm, and 1000mm or more without breaking. In the examples having a "drop ball impact test height", the crystallized glass product is the test subject. In the examples, test data of 1000mm is recorded, which shows that the crystallized glass product withstood the impact without breaking even when a steel ball was dropped from a height of 1000mm. The drop ball impact test height in the present invention may be abbreviated to the drop ball height.

[0279] [Ball drop height] A 145mm x 67mm x 0.7mm crystallized glass sample is placed on a glass support jig, and a 32g steel ball is dropped from a specified height. The maximum drop test height at which the sample can withstand the impact without breaking is defined as the main body drop height. Specifically, the test is performed from a drop test height of 500mm, and the height is changed sequentially to 550mm, 600mm, 650mm, and 700mm or more without breaking. In the embodiment having the "main body drop height", the crystallized glass is the test object, that is, the drop ball impact test height of the crystallized glass. In the embodiment, test data of 1000mm is recorded, which shows that the glass can withstand the impact without breaking even when a steel ball is dropped from a height of 1000mm.

[0280] [Fracture toughness] A method was used to directly measure the dimensions of the indentation-expanded crack. The sample dimensions were 2mm x 4mm x 20mm. After the sample was prepared by chamfering, flattening and polishing, a force of 49N was applied to the sample with a Vickers hardness indenter and maintained for 30 seconds to create an indentation, and then the fracture strength was measured using a three-point bending method.

[0281] [4-point bending strength] The test was performed using a microcomputer-controlled electronic universal testing machine CMT6502, with a sample specification of 1 mm or less in thickness, and standardized on ASTM C 158-2002. In the present invention, the four-point bending strength may be simply referred to as bending strength.

[0282] [Vickers hardness] It is expressed as the load (N) applied when a diamond pyramid indenter with an angle of 136° between the opposing faces presses a pyramid-shaped indentation into the test surface, divided by the surface area (mm^2) calculated from the length of the indentation. The test was performed with a load of 100 (N) and a holding time of 15 (seconds). In the present invention, Vickers hardness may be simply called hardness.

[0283] [|B|value] The B value is measured using a Minolta CM-700d. The sample standard is a thickness of 1mm or less, and the set correction long tube and short tube are used to perform zero position calibration and whiteboard calibration of the equipment, respectively. After calibration, the long tube is used to perform an air test to determine the stable calibration reliability of the equipment (B≦0.05). After passing the equipment correction, the product is placed on the zero position long tube and tested. The |B| value is the absolute value of the B value.

[0284] [Thermal expansion coefficient] Thermal expansion coefficient (α 20℃-120℃ ) was tested according to the GB / T7962.16-2010 test method.

[0285] [Refractive index] Refractive index (n d ) was tested according to the method of GB / T7962.1-2010.

[0286] [Dielectric constant] Dielectric constant (ε r ) was measured according to GB 9622.9-1988 method, and the measurement frequency was 1 to 7 GHz.

[0287] [Dielectric loss] The dielectric loss (tan δ) is measured according to the method of GB 9622.9-1988, and the measurement frequency is 1 to 7 GHz.

[0288] [Surface resistance] The surface resistance was tested according to the CS-157-2020 method at a test temperature of 20 to 40°C.

[0289] The crystallized glass product of the present invention has the following properties: 1) In some embodiments, the four-point bending strength of the crystallized glass product is 600 MPa or more, preferably 650 MPa or more, and more preferably 700 MPa or more. 2) In some embodiments, the depth of the ion exchange layer of the crystallized glass article is 20 μm or more, preferably 30 μm or more, more preferably 40 μm or more. 3) In some embodiments, the crystallized glass product has a ball drop impact test height of 1400 mm or more, preferably 1500 mm or more, more preferably 1600 mm or more. 4) In some embodiments, the crystallized glass product has a fracture toughness of 1 MPa m 1 / 2 More than 1.3 MPa m 1 / 2 or more, and more preferably 1.5MPa·m^1 / 2 or more. 5) In some embodiments, the crystallized glass product has a Vickers hardness (Hv) of 730 kgf / mm 2 More than 750kgf / mm 2 More preferably, 780kgf / mm 2 That's all. 6) In some embodiments, the crystallization of the crystallized glass product is 50% or more, preferably 60% or more, and more preferably 70% or more. 7) In some embodiments, the crystallized glass product has a grain size of 80 nm or less, preferably 50 nm or less, and more preferably 30 nm or less. 8) In some embodiments, the haze of a crystallized glass product having a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 9) In some embodiments, the crystallized glass product having a thickness of 1 mm or less has an average light transmittance of 87% or more, preferably 89% or more, more preferably 90% or more at a wavelength of 400 to 800 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 10) In some embodiments, the crystallized glass product having a thickness of 1 mm or less has a light transmittance of 88% or more, preferably 90% or more, more preferably 91% or more at a wavelength of 550 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 11) In some embodiments, the crystallized glass product having a thickness of 1 mm or less has an average light |B| value at 400 to 800 nm of 0.9 or less, preferably 0.8 or less, more preferably 0.7 or less. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 12) In some embodiments, the dielectric constant (ε r ) is 5.4 or more, preferably 5.8 or more, and more preferably 6.0 or more. 13) In some embodiments, the dielectric loss (tan δ) of the crystallized glass product is 0.05 or less, preferably 0.04 or less, more preferably 0.02 or less, more preferably 0.01 or less.

[0290] The crystallized glass of the present invention has the following properties: 1) In some embodiments, the crystallinity of the glass-ceramics is 50% or more, preferably 60% or more, and more preferably 70% or more. 2) In some embodiments, the grain size of the glass-ceramics is 80 nm or less, preferably 50 nm or less, preferably 30 nm or less. 3) In some embodiments, the haze of the crystallized glass having a thickness of 1 mm or less is 0.2% or less, preferably 0.18% or less, more preferably 0.15% or less. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 4) In some embodiments, the crystallized glass having a thickness of 1 mm or less has an average light transmittance of 87% or more, preferably 89% or more, more preferably 90% or more at a wavelength of 400 to 800 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 5) In some embodiments, the crystallized glass having a thickness of 1 mm or less has a light transmittance of 88% or more, preferably 90% or more, more preferably 91% or more at a wavelength of 550 nm. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 6) In some embodiments, the body drop height of the crystallized glass is 1700 mm or more, preferably 1900 mm or more, and more preferably 2000 mm or more. 7) In some embodiments, the crystallized glass having a thickness of 1 mm or less has an average light |B| value of 0.9 or less at 400 to 800 nm, preferably 0.8 or less, more preferably 0.7 or less. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, even more preferably 0.5 to 0.8 mm, and most preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm. 8) In some embodiments, the Vickers hardness (Hv) of the crystallized glass is 630 kgf / mm 2 More than 650kgf / mm 2 More preferably, 680kgf / mm 2 That's all. 9) In some embodiments, the thermal expansion coefficient (α 20℃-120℃ ) is 70 x 10 -7 / K~90×10 -7 / K. 10) In some embodiments, the refractive index (nd) of the crystallized glass is 1.5520 to 1.5700. 11) In some embodiments, the dielectric constant (ε r) is 5.4 or more, preferably 5.8 or more, and more preferably 6.0 or more. 12) In some embodiments, the dielectric loss (tan δ) of the crystallized glass is 0.05 or less, preferably 0.04 or less, more preferably 0.03 or less, and even more preferably 0.01 or less. 13) In some embodiments, the surface resistance of the crystallized glass is 1×10 9 Ω cm or more, preferably 1×10 10 Ω cm or more, preferably 1×10 11 Ω·cm or more.

[0291] The glass composition of the present invention has the following properties. 1) In some embodiments, the thermal expansion coefficient (α 20℃-120℃ ) is 65 x 10 -7 / K~80×10 -7 / K. 2) In some embodiments, the refractive index (nd) of the glass composition is 1.5400 to 1.5600.

[0292] The crystallized glass, crystallized glass product, glass composition, glass molded body, and crystallized glass molded body of the present invention have the above-mentioned excellent properties, so they can be widely manufactured as glass covers and glass parts. At the same time, the crystallized glass, crystallized glass product, glass composition, glass molded body, and crystallized glass molded body of the present invention can be applied to electronic devices and display devices, such as mobile phones, watches, personal computers, and touch displays. Protective glass used in the manufacture of mobile phones, smartphones, tablets, notebook computers, PDAs, televisions, personal computers, MTA machines, or industrial displays, or used in the manufacture of touch screens, protective windows, automobile windows, train windows, aircraft windows, touch screen protective glass, hard disk substrates or solar cell substrates, or used in the manufacture of white goods such as refrigerator parts or cookware. EXAMPLES

[0293] In order to more clearly illustrate and explain the technical aspects of the present invention, the following non-limiting embodiments are provided. Although the embodiments of the present invention make great efforts to ensure the accuracy of numerical values ​​(e.g., quantities, temperatures, etc.), some errors and deviations must be considered. The compositions themselves are given in mass percent for the oxides and are normalized to 100%.

[0294] <Glass Composition Examples> In this embodiment, the above-mentioned method for producing a glass composition can be used to obtain glass compositions having the compositions shown in Tables 1 to 6. In addition, the characteristics of each glass composition were measured by the test method according to the present invention, and the measurement results are shown in Tables 1 to 6.

[0295] [Table 1]

[0296] [Table 2]

[0297] [Table 3]

[0298] [Table 4]

[0299] [Table 5]

[0300] [Table 6]

[0301] <Examples of glass-ceramics> In the embodiment of the present invention, the above-mentioned manufacturing method of crystallized glass can be used to obtain crystallized glass having the composition shown in Tables 7 to 12. In addition, the characteristics of each crystallized glass are measured by the test method according to the present invention, and the measurement results are shown in Tables 7 to 12, but the temperature is 25°C, which is room temperature as described in the following examples.

[0302] [Table 7]

[0303] [Table 8]

[0304] [Table 9]

[0305] [Table 10]

[0306] [Table 11]

[0307] [Table 12]

[0308] [Table 13]

[0309] [Table 14]

[0310] [Table 15]

[0311] [Table 16]

[0312] [Table 17]

[0313] [Table 18]

[0314] <Examples of crystallized glass products> In the embodiment of the present invention, the above-mentioned manufacturing method of the crystallized glass product can be used to obtain the crystallized glass products having the compositions shown in Tables 13 to 18. In addition, the characteristics of each crystallized glass are measured by the test method of the present invention, and the measurement results are shown in Tables 13 to 18.

[0315] [Table 19]

[0316] [Table 20]

[0317] [Table 21]

[0318] [Table 22]

[0319] [Table 23]

[0320] [Table 24]

[0321]

Table 25

[0322]

Table 26

[0323]

Table 27

[0324]

Table 28

[0325]

Table 29

[0326]

Table 30

Claims

1. A crystallized glass product having a composition, in mass percent, of SiO 2 Ingredients: 55-80%, Al 2 O 3 Ingredients less than 10%, Li 2 O component 8-25%, ZrO 2 Ingredients: 5-15%, P 2 O 5 A crystallized glass product characterized by containing 1 to 8% of the component.

2. The crystallized glass product according to claim 1, the composition of which is, in mass percent, K 2 O component 0-5%, and / or MgO component 0-3%, and / or ZnO component 0-3%, and / or Na 2 O component 0-6%, and / or SrO component 0-5%, and / or BaO component 0-5%, and / or CaO component 0-5%, and / or TiO 2 Component 0-5% and / or B 2 O 3 Component 0-5% and / or Y 2 O 3 A crystallized glass product comprising 0-6% of a component and / or 0-2% of a fining agent component.

3. The composition is SiO 2 , Al 2 O 3 , Li 2 O, ZrO 2 , P 2 1. A crystallized glass product comprising O, wherein a crystalline phase of said crystallized glass product comprises a lithium silicate crystalline phase that is higher in mass percent than other crystalline phases.

4. The composition is SiO 2 , Li 2 O, ZrO 2 , P 2 A crystallized glass product containing O, characterized in that the crystallized glass product has a thickness of 1 mm or less and an average light |B| value of 400 to 800 nm is 0.9 or less.

5. The crystallized glass product according to claim 3 or 4, the composition of which is, in mass percent, SiO 2 Ingredients: 55-80% and / or Al 2 O 3 Ingredients less than 10% and / or Li 2 O content 8 to 25% and / or ZrO 2 Ingredients: 5-15% and / or P 2 O 5 Ingredients 1-8% and / or K 2 O component 0-5%, and / or MgO component 0-3%, and / or ZnO component 0-3%, and / or Na 2 O component 0-6%, and / or SrO component 0-5%, and / or BaO component 0-5%, and / or CaO component 0-5%, and / or TiO 2 Component 0-5% and / or B 2 O 3 Component 0-5% and / or Y 2 O 3 A crystallized glass product comprising 0-6% of a component and / or 0-2% of a fining agent component.

6. A crystallized glass product according to any one of claims 1 to 4, characterized in that its composition, in mass percent, satisfies one or more of the following 12 conditions: 1) Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 1.2 or less, preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 1.0 or less, more preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 0.05 to 0.7, more preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 0.1 to 0.6, more preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 0.3-0.5; 2) SiO 2 / ZrO 2 is 4.0 to 15.8, preferably SiO 2 / ZrO 2 is 4.5 to 12.0, more preferably SiO 2 / ZrO 2 is 5.0 to 9.5, more preferably SiO 2 / ZrO 2 is 6.0 to 9.0, more preferably SiO 2 / ZrO 2 is 6.5-7.5; 3) P 2 O 5 +ZrO 2 Ingredients are 6-21%, preferably P 2 O 5 +ZrO 2 The content is 7-18%, preferably P 2 O 5 +ZrO 2 The content is 8-16%, preferably P 2 O 5 +ZrO 2 The component is 10-16%, more preferably P 2 O 5 +ZrO 2 The composition is 10.5-14%; 4) SiO 2 / (P 2 O 5 +ZrO 2 ) is 2.5 to 12.0, preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 3.5 to 7.5, more preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 4.0 to 6.5, more preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 4.5 to 6.0, more preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 5.0-6.0; 5) (ZrO 2 +Li 2 O) / Al 2 O 3 is 2.0 or more, preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 2.5 to 30.0, more preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 2.8 to 10.0, more preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 3.0 to 8.0, more preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 3.5-6.0; 6) (SiO 2 +Al 2 O 3 ) / ZrO 2 is 4.0 to 16.0, preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 5.0 to 10.0, more preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 6.0 to 9.5, more preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 6.5 to 9.0, more preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 7.0-8.0; 7) (Li 2 O+ZrO 2 ) / SiO 2 is 0.19 to 0.55, preferably (Li 2 O+ZrO 2 ) / SiO 2 is 0.2 to 0.5, more preferably (Li 2 O+ZrO 2 ) / SiO 2 is 0.25 to 0.45, more preferably (Li 2 O+ZrO 2 ) / SiO 2 is 0.25 to 0.4, more preferably (Li 2 O+ZrO 2 ) / SiO 2 is between 0.3 and 0.4; 8) (MgO + ZnO) / ZrO 2 is 0.65 or less, preferably (MgO+ZnO) / ZrO 2 is 0.4 or less, and more preferably (MgO+ZnO) / ZrO 2 is 0.2 or less, and more preferably (MgO+ZnO) / ZrO 2 is 0.1 or less, and more preferably (MgO+ZnO) / ZrO 2 is less than or equal to 0.05; 9) (Li 2 O+Al 2 O 3 ) / ZrO 2 is 0.8 to 5.0, preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.0 to 4.0, more preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.2 to 3.0, more preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.5 to 2.5, more preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.7-2.3; 10) Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.5 to 3.0, preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.6 to 2.5, more preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.7 to 2.0, more preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.8 to 1.5, more preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.9-1.3; 11) Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.4 or less, preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.3 or less, more preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.01 to 0.3, more preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.05 to 0.3, more preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is between 0.1 and 0.25; 12) Al 2 O 3 / Li 2 O is 0.7 or less, preferably Al 2 O 3 / Li 2 O is 0.6 or less, and more preferably Al 2 O 3 / Li 2 O is 0.01 to 0.6, and more preferably Al 2 O 3 / Li 2 O is 0.05 to 0.55, and more preferably Al 2 O 3 / Li 2 O is 0.1 to 0.

5.

7. The crystallized glass product according to any one of claims 1 to 4, the composition of which is, in mass percent, SiO 2 The component is 58-78%, preferably SiO 2 The component is 62-72%, more preferably SiO 2 Ingredients: 63-69% and / or Al 2 O 3 The composition is 0.1 to 8%, preferably Al. 2 O 3 The component is 1 to 7%, preferably Al 2 O 3 Ingredients: 2-6.5% and / or Li 2 O content 9 to 22%, preferably Li 2 O component 10 to 20%, more preferably Li 2 O content 11-18% and / or ZrO 2 Components: 6-12%, preferably ZrO 2 The component is 6 to 10%, preferably ZrO 2 Ingredients 6.5-9.5% and / or P 2 O 5 Components are 1.5 to 7%, preferably P 2 O 5 Ingredients 2-6% and / or K 2 O component 0 to 4%, preferably K 2 O component 0-2%, and / or MgO component 0-2%, preferably MgO component 0-1%, and / or ZnO component 0-2%, preferably ZnO component 0-1%, and / or Na 2 O component 0 to 4%, preferably Na 2 O component 0.5 to 3%, and / or SrO component 0 to 2%, preferably SrO component 0 to 1%, and / or BaO component 0 to 2%, preferably BaO component 0 to 1%, and / or CaO component 0 to 2%, preferably CaO component 0 to 1%, and / or TiO 2 Component is 0-2%, preferably TiO 2 Component 0-1% and / or B 2 O 3 Component is 0-3%, preferably B 2 O 3 Component 0-2% and / or Y 2 O 3 Component is 0-4%, preferably Y 2 O 3 13. A crystallized glass product comprising 0-2% of a component and / or 0-1% of a fining agent component, preferably 0-0.5% of a fining agent component.

8. The crystallized glass product according to any one of claims 1 to 4, the composition of which is, in mass percent, La 2 O 3 +Gd 2 O 3 +Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 Contains 0-2% of the following elements, and / or does not contain SrO, and / or does not contain BaO, and / or does not contain MgO, and / or does not contain CaO, and / or does not contain ZnO, and / or does not contain PbO, and / or As 2 O 3 Does not contain and / or TiO 2 does not contain and / or B 2 O 3 Does not contain and / or Y 2 O 3 and / or F-free.

9. The crystallized glass product according to any one of claims 1 to 4, wherein the crystal phase contains a lithium silicate crystal phase, and / or a lithium phosphate crystal phase, and / or a petalite crystal phase, and / or a quartz solid solution crystal phase.

10. 5. The crystallized glass product according to claim 1, characterized in that the crystal phase of the crystallized glass product comprises a lithium silicate crystal phase which is higher in mass percentage than other crystal phases, and the lithium silicate crystal phase represents 10-70%, preferably 15-60%, of the crystallized glass product.

11. A crystallized glass product according to any one of claims 1 to 4, characterized in that the crystal phase of the crystallized glass contains a lithium silicate crystal phase having a mass percentage higher than that of other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is 30 to 65%, preferably 40 to 55%.

12. 5. A crystallized glass product according to any one of claims 1 to 4, characterized in that the crystal phase of the crystallized glass contains a lithium disilicate crystal phase that is higher in mass percentage than other crystal phases, and the mass percentage of the lithium disilicate crystal phase in the crystallized glass is 10 to 60%, preferably 15 to 50%, preferably 20 to 45%.

13. A crystallized glass product according to any one of claims 1 to 4, characterized in that the crystallized glass contains a lithium phosphate crystal phase, and the mass percentage of the lithium phosphate crystal phase in the crystallized glass is 5% or less, and / or the crystallized glass contains a quartz solid solution crystal phase, and the mass percentage of the quartz solid solution crystal phase in the crystallized glass is 5% or less.

14. The crystallized glass product according to any one of claims 1 to 4, characterized in that the crystallized glass contains a petalite crystal phase, and the mass percentage of the petalite crystal phase in the crystallized glass is 18% or less, preferably 10% or less, and more preferably 5% or less.

15. The crystallized glass product according to any one of claims 1 to 4, characterized in that its composition has a four-point bending strength of 600 MPa or more, preferably 700 MPa or more; and / or an ion-exchange layer depth of 20 μm or more, preferably 40 μm or more; and / or a falling ball impact test height of 1400 mm or more, preferably 1600 mm or more; and / or a fracture toughness of 1 MPa m 1 / 2 More than 1.5 Mpa m, preferably 1.5 Mpa m 1 / 2 and / or Vickers hardness is 730 kgf / mm 2 More than 780kgf / mm 2 and / or a dielectric constant ε r and / or a crystallinity of 50% or more, preferably 70% or more; and / or a crystal grain size of 80 nm or less, preferably 30 nm or less; and / or a haze of 0.2% or less, preferably 0.15% or less in a crystallized glass product having a thickness of 1 mm or less; and / or an average light transmittance at wavelengths of 400 to 800 nm in a crystallized glass product having a thickness of 1 mm or less of 87% or more, preferably 90% or more; and / or an average light transmittance at wavelengths of 550 nm in a crystallized glass product having a thickness of 1 mm or less of 88% or more, preferably 91% or more; and / or an average light |B| value at 400 to 800 nm in a crystallized glass product having a thickness of 1 mm or less of 0.9 or less, preferably 0.7 or less.

16. The crystallized glass product according to any one of claims 1 to 4, containing a coloring agent, the coloring agent being, in mass percent, 0 to 4% NiO component, and / or Ni 2 O 3 0-4% of CoO and / or 0-2% of Co 2 O 3 Ingredients: 0-2% and / or Fe 2 O 3 Ingredients: 0-7% and / or MnO 2 Ingredients: 0-4% and / or Er 2 O 3 Ingredients: 0-8% and / or Nd 2 O 3 Ingredients: 0-8% and / or Cu 2 O content 0-4% and / or Pr 2 O 3 Ingredients: 0-8% and / or CeO 2 A crystallized glass product characterized by containing 0 to 4% of the component.

17. A crystallized glass having a composition, in mass percent, of SiO 2 Ingredients: 55-80%, Al 2 O 3 Ingredients less than 10%, Li 2 O component 8-25%, ZrO 2 Ingredients: 5-15%, P 2 O 5 A crystallized glass characterized by containing 1 to 8% of the component.

18. The crystallized glass according to claim 17, the composition of which is, in mass percent, K 2 O component 0-5%, and / or MgO component 0-3%, and / or ZnO component 0-3%, and / or Na 2 O component 0-6%, and / or SrO component 0-5%, and / or BaO component 0-5%, and / or CaO component 0-5%, and / or TiO 2 Component 0-5% and / or B 2 O 3 Component 0-5% and / or Y 2 O 3 2. A crystallized glass comprising 0-6% of a component and / or 0-2% of a fining agent component.

19. The composition is SiO 2 , Al 2 O 3 , Li 2 O, ZrO 2 , P 2 1. A crystallized glass containing O, the crystallized glass having a crystal phase containing a lithium silicate crystal phase having a mass percentage higher than other crystal phases.

20. 1. A crystallized glass containing a lithium silicate crystal phase, the crystallized glass having a ball drop test height of 1700 mm or more.

21. The crystallized glass according to claim 19 or 20, the composition of which is, in mass percent, SiO 2 Ingredients: 55-80% and / or Al 2 O 3 Ingredients less than 10% and / or Li 2 O content 8 to 25% and / or ZrO 2 Ingredients: 5-15% and / or P 2 O 5 Ingredients 1-8% and / or K 2 O component 0-5%, and / or MgO component 0-3%, and / or ZnO component 0-3%, and / or Na 2 O component 0-6%, and / or SrO component 0-5%, and / or BaO component 0-5%, and / or CaO component 0-5%, and / or TiO 2 Component 0-5% and / or B 2 O 3 Component 0-5% and / or Y 2 O 3 2. A crystallized glass comprising 0-6% of a component and / or 0-2% of a fining agent component.

22. The crystallized glass according to any one of claims 17 to 20, characterized in that its composition, in mass percent, satisfies one or more of the following 12 conditions: 1) Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 1.2 or less, preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 1.0 or less, more preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 0.05 to 0.7, more preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 0.1 to 0.6, more preferably Al 2 O 3 / (P 2 O 5 +ZrO 2 ) is 0.3-0.5; 2) SiO 2 / ZrO 2 is 4.0 to 15.8, preferably SiO 2 / ZrO 2 is 4.5 to 12.0, more preferably SiO 2 / ZrO 2 is 5.0 to 9.5, more preferably SiO 2 / ZrO 2 is 6.0 to 9.0, more preferably SiO 2 / ZrO 2 is 6.5-7.5; 3) P 2 O 5 +ZrO 2 Ingredients are 6-21%, preferably P 2 O 5 +ZrO 2 The content is 7-18%, preferably P 2 O 5 +ZrO 2 The content is 8-16%, preferably P 2 O 5 +ZrO 2 The component is 10-16%, more preferably P 2 O 5 +ZrO 2 The composition is 10.5-14%; 4) SiO 2 / (P 2 O 5 +ZrO 2 ) is 2.5 to 12.0, preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 3.5 to 7.5, more preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 4.0 to 6.5, more preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 4.5 to 6.0, more preferably SiO 2 / (P 2 O 5 +ZrO 2 ) is 5.0-6.0; 5) (ZrO 2 +Li 2 O) / Al 2 O 3 is 2.0 or more, preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 2.5 to 30.0, more preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 2.5 to 10.0, more preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 3.0 to 8.0, more preferably (ZrO 2 +Li 2 O) / Al 2 O 3 is 3.5-6.0; 6) (SiO 2 +Al 2 O 3 ) / ZrO 2 is 4.0 to 16.0, preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 5.0 to 10.0, more preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 6.0 to 9.5, more preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 6.5 to 9.0, more preferably (SiO 2 +Al 2 O 3 ) / ZrO 2 is 7.0-8.0; 7) (Li 2 O+ZrO 2 ) / SiO 2 is 0.19 to 0.55, preferably (Li 2 O+ZrO 2 ) / SiO 2 is 0.2 to 0.5, more preferably (Li 2 O+ZrO 2 ) / SiO 2 is 0.25 to 0.45, more preferably (Li 2 O+ZrO 2 ) / SiO 2 is 0.25 to 0.4, more preferably (Li 2 O+ZrO 2 ) / SiO 2 is between 0.3 and 0.4; 8) (MgO + ZnO) / ZrO 2 is 0.65 or less, preferably (MgO+ZnO) / ZrO 2 is 0.4 or less, and more preferably (MgO+ZnO) / ZrO 2 is 0.2 or less, and more preferably (MgO+ZnO) / ZrO 2 is 0.1 or less, and more preferably (MgO+ZnO) / ZrO 2 is less than or equal to 0.05; 9) (Li 2 O+Al 2 O 3 ) / ZrO 2 is 0.8 to 5.0, preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.0 to 4.0, more preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.2 to 3.0, more preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.5 to 2.5, more preferably (Li 2 O+Al 2 O 3 ) / ZrO 2 is 1.7-2.3; 10) Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.5 to 3.0, preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.6 to 2.5, more preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.7 to 2.0, more preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.8 to 1.5, more preferably Li 2 O / (ZrO 2 +P 2 O 5 ) is 0.9-1.3; 11) Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.4 or less, preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.3 or less, more preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.01 to 0.3, more preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is 0.05 to 0.3, more preferably Al 2 O 3 / (Li 2 O+ZrO 2 +P 2 O 5 ) is between 0.1 and 0.25; 12) Al 2 O 3 / Li 2 O is 0.7 or less, preferably Al 2 O 3 / Li 2 O is 0.6 or less, and more preferably Al 2 O 3 / Li 2 O is 0.01 to 0.6, and more preferably Al 2 O 3 / Li 2 O is 0.05 to 0.55, and more preferably Al 2 O 3 / Li 2 O is 0.1 to 0.

5.

23. The crystallized glass according to any one of claims 17 to 20, the composition of which is, in mass percent, SiO 2 The component is 58-78%, preferably SiO 2 The component is 62-72%, more preferably SiO 2 Ingredients: 63-69% and / or Al 2 O 3 The composition is 0.1 to 8%, preferably Al. 2 O 3 The component is 1 to 7%, preferably Al 2 O 3 Ingredients: 2-6.5% and / or Li 2 O content 9 to 22%, preferably Li 2 O component 10 to 20%, more preferably Li 2 O content 11-18% and / or ZrO 2 Components: 6-12%, preferably ZrO 2 The component is 6 to 10%, preferably ZrO 2 Ingredients 6.5-9.5% and / or P 2 O 5 Components are 1.5 to 7%, preferably P 2 O 5 Ingredients 2-6% and / or K 2 O component 0 to 4%, preferably K 2 O component 0-2%, and / or MgO component 0-2%, preferably MgO component 0-1%, and / or ZnO component 0-2%, preferably ZnO component 0-1%, and / or Na 2 O component 0 to 4%, preferably Na 2 O component 0.5 to 3%, and / or SrO component 0 to 2%, preferably SrO component 0 to 1%, and / or BaO component 0 to 2%, preferably BaO component 0 to 1%, and / or CaO component 0 to 2%, preferably CaO component 0 to 1%, and / or TiO 2 Component is 0-2%, preferably TiO 2 Component 0-1% and / or B 2 O 3 Component is 0-3%, preferably B 2 O 3 Component 0-2% and / or Y 2 O 3 Component is 0-4%, preferably Y 2 O 3 2. A crystallized glass comprising 0 to 2% of a component and / or 0 to 1% of a fining agent component, preferably 0 to 0.5% of a fining agent component.

24. The crystallized glass according to any one of claims 17 to 20, the composition of which is, in mass percent, La 2 O 3 +Gd 2 O 3 +Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 Contains 0-2% of the following elements, and / or does not contain SrO, and / or does not contain BaO, and / or does not contain MgO, and / or does not contain CaO, and / or does not contain ZnO, and / or does not contain PbO, and / or As 2 O 3 Does not contain and / or TiO 2 does not contain and / or B 2 O 3 Does not contain and / or Y 2 O 3 and / or F.

25. The crystallized glass according to any one of claims 17 to 20, wherein the crystal phase contains a lithium silicate crystal phase, and / or a lithium phosphate crystal phase, and / or a petalite crystal phase, and / or a quartz solid solution crystal phase.

26. The crystallized glass according to any one of claims 17 to 20, characterized in that the crystal phase of the crystallized glass contains a lithium silicate crystal phase having a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is 10 to 70%, preferably 15 to 60%.

27. The crystallized glass according to any one of claims 17 to 20, characterized in that the crystal phase of the crystallized glass contains a lithium silicate crystal phase having a higher mass percentage than other crystal phases, and the mass percentage of the lithium silicate crystal phase in the crystallized glass is 30 to 65%, preferably 40 to 55%.

28. The crystallized glass according to any one of claims 17 to 20, characterized in that the crystal phase of the crystallized glass contains a lithium disilicate crystal phase that is higher in weight percentage than other crystal phases, and the mass percentage of the lithium disilicate crystal phase in the crystallized glass is 10 to 60%, preferably 15 to 50%, and more preferably 20 to 45%.

29. The crystallized glass according to any one of claims 17 to 20, characterized in that the crystallized glass contains a lithium phosphate crystal phase, and the mass percentage of the lithium phosphate crystal phase in the crystallized glass is 5% or less, and / or the crystallized glass contains a quartz solid solution crystal phase, and the mass percentage of the quartz solid solution crystal phase in the crystallized glass is 5% or less.

30. The crystallized glass according to any one of claims 17 to 20, characterized in that the crystallized glass contains a petalite crystal phase, and the mass percentage of the petalite crystal phase in the crystallized glass is 18% or less, preferably 10% or less, and more preferably 5% or less.

31. The crystallized glass according to any one of claims 17 to 20, having a crystallinity of 50% or more, preferably 70% or more; and / or a grain size of 80 nm or less, preferably 30 nm or less; and / or a thermal expansion coefficient of 70×10 -7 / K~90×10 -7 / K; and / or the refractive index is 1.5520 to 1.5700; and / or the body drop height is 1700 mm or more, preferably 2000 mm or more; and / or the Vickers hardness is 630 kgf / mm 2 More than 680kgf / mm 2 and / or a relative dielectric constant of 5.4 or more, preferably 6.0 or more; and / or a dielectric loss of 0.05 or less, preferably 0.03 or less; and / or a surface resistance of 1×10 9 Ω cm or more, preferably 1×10 11 and / or the haze of the crystallized glass having a thickness of 1 mm or less is 0.2% or less, preferably 0.15% or less; and / or the average light transmittance of the crystallized glass having a wavelength of 400 to 800 nm is 87% or more, preferably 90% or more, and / or the light transmittance of the crystallized glass having a thickness of 1 mm or less is 88% or more, preferably 91% or more, and / or the average light |B| value of the crystallized glass having a thickness of 1 mm or less at 400 to 800 nm is 0.9 or less, preferably 0.7 or less.

32. The crystallized glass according to any one of claims 17 to 20, containing a colorant, the colorant being, in mass percent, 0 to 4% NiO component, and / or Ni 2 O 3 0-4% of CoO and / or 0-2% of Co 2 O 3 Ingredients: 0-2% and / or Fe 2 O 3 Ingredients: 0-7% and / or MnO 2 Ingredients: 0-4% and / or Er 2 O 3 Ingredients: 0-8% and / or Nd 2 O 3 Ingredients: 0-8% and / or Cu 2 O content 0-4% and / or Pr 2 O 3 Ingredients: 0-8% and / or CeO 2 A crystallized glass characterized by containing 0 to 4% of the component.

33. A glass cover comprising the crystallized glass product according to any one of claims 1 to 4.

34. A glass part comprising the crystallized glass product according to any one of claims 1 to 4.

35. A display device comprising the crystallized glass product according to any one of claims 1 to 4.

36. 5. An electronic device comprising the crystallized glass product according to claim 1.

Citation Information

Patent Citations

  • Glass ceramic substrate for information storage medium

    JP2000233941A

  • LITHIUM SILICATE GLASS CERAMIC, AND GLASS CONTAINING ZrO2 CONTENT

    JP2011225441A

  • Dental restorative material, method for manufacturing the same, and ingot

    JP2014524906A

  • High-strength glass ceramic having a petalite and lithium silicate structure

    JP2017530933A